Mechanical and electrostatic filter media
By using electrospinning technology to arrange nanoparticles and enhance electrostatic charges in nonwoven filter media, the problems of low capture efficiency and short life of filter media in the prior art are solved, and efficient capture of submicron particles and extended filter life are achieved. Effect.
Patent Information
- Application Number
- CN202380041736.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-08
- Filing Date
- 2023-04-07
- Publication Date
- 2025-01-07
AI Technical Summary
Existing nonwoven filter media are less efficient in capturing submicron particles, electrostatic charge attenuation leads to a shortening of the filter life, and uneven dispersion of nanoparticles leads to a decrease in dust capacity, affecting the commercial potential of the filter.
Electrospinning technology is used to arrange nanoparticles in nonwoven substrates, and the electrostatic charge is enhanced by triboelectric or corona discharge method to ensure that the nanoparticles are evenly dispersed throughout the filter media, and the filtration efficiency and dust capacity are improved.
It improves the capture efficiency of the filter media for submicron particles, extends the service life of the filter, enhances the dust capacity, maintains the air flow, and improves the overall performance of the filter.
Smart Images

Figure BDA0005143734350000421 
Figure BDA0005143734350000431 
Figure BDA0005143734350000432
Abstract
Description
[0001] Citation to Related Applications
[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 328,970, filed April 8, 2022, the entire disclosure of which is incorporated herein by reference for all purposes. This application is also related to commonly assigned, co-pending U.S. Provisional Patent Application Nos. 63 / 328,983, 63 / 328,998, 63 / 328,959, 63 / 329,009, 63 / 329,018, 63 / 329,137, 63 / 329,146, 63 / 329,155, 63 / 329,158, 63 / 329,161, and 63 / 329,162, all of which were filed on April 8, 2022, the entire disclosures of which are incorporated herein by reference for all purposes. Technical Field
[0003] The present specification generally relates to filter media and filters containing nanoparticles and electrostatic charges for filtering contaminants by mechanical and electrostatic means. Background Art
[0004] Nonwoven materials generally include a structure of individual fibers or threads that are interwoven with one another, but not in an identifiable manner as in a knitted or woven fabric. Such nonwoven materials are used in many applications, such as household cleaning products, roofing and flooring products, automotive interiors and headliners, reusable bags, wall coverings, filtration devices, insulation materials, etc.
[0005] Due to their fine fiber size, nonwoven materials are particularly useful for capturing contaminants in filtration devices. The fibers of the filter media are measured in microns and can be formed by spunbonding, meltblowing, electrospinning or other techniques. When fluid flows through the filter media, the fine fibers capture and retain contaminants in the filter media.
[0006] The two main types of filtration devices that incorporate nonwoven materials include surface filters and depth filters. Surface filters, such as membrane layers or films, act as a barrier to capture contaminants before they enter the media structure. These surface filters typically have submicron pore sizes and narrow pore size distributions. Surface filters tend to have higher particle capture efficiencies. However, they also have higher pressure drops and low dust holding capacity. High pressure drops result in reduced air flow through the filter. Low dust loading capacity significantly reduces filter life. As a result, surface filters have limited application in the air filtration industry.
[0007] Depth filters are commonly used in air filtration units with medium to high efficiency, low pressure drop, and relatively high dust holding capacity. Traditional residential and commercial air filters, such as HEPA filters, are generally rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values indicating greater efficiency in capturing specific types of particles.
[0008] Pollutants come in a wide range of sizes. However, pollutants smaller than 1 micron are the most harmful particles to the human body and are relatively difficult to filter. For example, traditional mechanical air filters typically report a MERV rating of about 8-10 for nonwoven filter materials. Therefore, these filter media typically do not capture submicron particles, such as viruses and other harmful pathogens.
[0009] The filtration industry has focused on two different methods of capturing these submicron particles: electrostatic forces and utilizing nanoparticles in the filter media. Electrostatic filters are formed by electrostatically charging the fibers within a nonwoven material using triboelectric methods, corona discharge, hydrocharging, electrospinning, or other known methods. Electrostatic filters are most effective at capturing submicron particles, fairly effective at capturing particles between 1 and 3 microns, and least effective at capturing larger particles between 3 and 10 microns. Electrostatic fibers are commonly used in many filtration applications, such as face masks and HEPA filters, to filter submicron contaminants, such as viruses, etc.
[0010] One disadvantage of electrostatic filters is that the electrostatic charge decays over time and with filter use. As a result, the efficiency of the filter decreases relatively quickly, shortening its life. For example, an electrostatic filter with an initial MERV rating of 13 may lose at least 2-3 MERV rating points after the electrostatic force decays. This compromises the integrity of the filter and may partially or completely inhibit its ability to capture submicron particles. Another approach to capturing submicron contaminants is to use nanoparticles in combination with the fibers. A filtration system may employ a filter media containing larger fibers with diameters measured in microns and smaller nanoparticles. Nanoparticles increase the surface area in the media for capturing particles by reducing the overall fiber size in the media. Nanoparticles also tend to squeeze against each other, thereby increasing the packing density within the filter media. It has been shown that even a small number of nano-sized fibers in a layer formed on a microfiber material can improve the filtration characteristics of the material.
[0011] The most common method of incorporating nanoparticles into filter media is to apply a very thin layer of continuous nanofibers on a nonwoven substrate by electrospinning. The nanoparticles typically extend parallel or perpendicular to the surface of the main filter media layer and provide efficient filtration of small particles in addition to the filtration of larger particles provided by the coarse filter media. For example, U.S. Pat. No. 6,743,273 discloses a filter media in which a continuous layer of nanofibers is deposited on the surface of the substrate. U.S. Pat. No. 10,799,820 also discloses an air filter media comprising a continuous layer of nanofibers on the surface of the filter media.
[0012] Although existing filter media incorporating nanoparticles have improved the relative efficiency of these filters, the commercial potential of these filters is limited in certain applications because the nanoparticles are typically dispersed onto the surface of the nonwoven material. The thinner layer of nanoparticles on the filter surface provides only limited particle filtration and has a relatively low dust holding capacity.
[0013] Although many attempts have been made to incorporate nanomaterials into filter media to improve overall filtration efficiency, these attempts have been limited to so-called "wet-laid" methods. These wet-laid methods involve incorporating chopped nanofibers into a liquid slurry to separate entangled nanofibers with the help of a surfactant. For example, U.S. Patent No. 10,252,201 discloses a filter medium made of a mixture of chopped nanofibers and chopped coarse fibers formed by a wet-laid method. Similarly, U.S. Patent Application No. 2021 / 0023813 discloses a method for manufacturing a composite structure consisting of a continuous fiber nonwoven substrate with discontinuous fibers (e.g., carbon nanofibers). The method includes pulling a continuous fiber nonwoven substrate through a slurry of discontinuous fibers, wherein the nanomaterial is embedded in the nonwoven substrate.
[0014] While these structures have demonstrated increased efficiency, they have also suffered from other issues such as reduced life and / or efficiency when the media is placed under normal use conditions. Additionally, these wet-laid processes have not been successful in incorporating the nanoparticles uniformly throughout the nonwoven material, which has resulted in agglomeration of the nanoparticles within the material, further reducing its efficiency and overall dust holding capacity.
[0015] Therefore, there is a need for an improved nonwoven material and a filter comprising such a material. It is desirable to increase the efficiency of such a filter in capturing pollutants, especially submicron-sized pollutants, without compromising other important properties of the filter, such as life, dust holding capacity, and pressure drop or air flow through the filter. Summary of the invention
[0016] The following is a brief summary of the claimed subject matter to provide a basic understanding of some aspects of the claimed subject matter. This summary is not an extensive overview of the claimed subject matter. It is not intended to identify key or critical elements of the claimed subject matter or to define the scope of the claimed subject matter. Its sole purpose is to present some concepts of the claimed subject matter in a concise form as a prelude to the more detailed description presented later.
[0017] Provided are a filter medium and filter, such as an air filter, a mask, a gas turbine and compressor intake filter, a panel filter, etc., which utilizes electrostatic forces and nanoparticles within the filter medium to capture submicron particles. Also provided are a system and method for manufacturing such a filter.
[0018] In one aspect, a filter medium includes a substrate including a substrate comprising fibers and nanoparticles disposed within the substrate. At least one of the fibers or the nanoparticles is electrostatically charged. The electrostatic charge effectively captures submicron particles, at least during the initial use of the filter. The nanoparticles ensure that the filter remains highly efficient even after the electrostatic charge begins to decay over time. In addition, the bonding between the fibers and the nanoparticles can be enhanced by the electrostatic charge, which causes the nanoparticles to be dispersed throughout the filter medium at a certain depth.
[0019] The fibers, nanoparticles, or both in the substrate can be electrostatically charged using triboelectric methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. Nanoparticles having different triboelectric properties relative to the fibers can be selected to enhance particle removal using the triboelectric effect. This enhances or creates a local electric field gradient within the filter media to enhance particle removal. The nanoparticles and macrofibers can have different wetting characteristics.
[0020] In some embodiments, the fibers are electrostatically charged so that mechanical filtration can be achieved using nanoparticles, while electrostatic filtration can be achieved through an electret substrate. The electrostatic or electret substrate can be a high-loft triboelectric filter medium made by combing and needling. In one embodiment, the nanoparticles are preferably deposited into the substrate before needling, and then the electrostatic fibers and nanoparticles are needled together.
[0021] In some embodiments, nanoparticles are dispersed in substrate "at a certain depth". As used herein, the term "at a certain depth" means that nanoparticles are dispersed across the first surface of substrate so that at least some nanoparticles are arranged between the first and second relative surfaces in the substrate or the internal structure of the medium. In some embodiments, nanoparticles are substantially dispersed throughout the entire medium from the first surface to the relative second surface. In other embodiments, nanoparticles are dispersed in a portion of the medium from the first surface to the position between the first and second surfaces. In other embodiments, nanoparticles are arranged from the first surface of substrate to the relative second surface with a density gradient. The density of nanoparticles can be larger at the first surface or second surface.
[0022] The nanoparticles increase the total surface area within the filter media, thereby increasing filtration efficiency and allowing capture of submicron contaminants without significantly compromising other factors, such as pressure drop (i.e., air flow) through the filter. In addition, the filters disclosed herein are able to withstand rigorous regulation, which allows the filter to achieve the same level of filtration performance throughout its life. In addition, these materials increase overall dust holding capacity, thereby extending the life of the filter, especially compared to filters that rely solely or primarily on electrostatic effects to increase efficiency.
[0023] In some embodiments, the fiber can have a linear density greater than about 3 deniers. The fiber in the air filter usually has a linear density of about 3 deniers or less to ensure that the fiber is small enough to capture pollutants passing through the filter. The applicant was surprised to find that by using nanoparticles dispersed in the filter medium, the fiber can have a larger linear density (e.g., greater than 3 deniers). This is because nanoparticles provide significant filtering capabilities. In some cases, the fiber can have a linear density greater than 3 deniers, 5 deniers or more, 6 deniers or more, or up to 7-10 deniers.
[0024] The substrate may include sheets, layers, films, apertured films, nets, meshes or other media. In certain embodiments, the substrate includes a nonwoven material having a structure of interwoven individual fibers or lines. Examples of suitable nonwoven materials include, but are not limited to, fibers, layers or webs processed by meltblowing, spunbonding, bonding carding, air-laid, co-forming, hydroentanglement, etc. In other embodiments, it is envisioned that knitted or woven fabrics are used as substrates.
[0025] In some embodiments, the filter comprises one or more support layers bonded to the filter medium. The support layer and / or the filter medium may include nanoparticles dispersed in the layer at a certain depth. In some embodiments, a polymer layer, membrane layer or membrane is provided, the polymer layer, membrane layer or membrane comprising one or more holes for gas or liquid to flow therethrough, and the nanoparticles are arranged in the polymer layer at a certain depth.
[0026] In certain embodiments, the nanoparticles are isolated in a fluid and dispersed through the first surface of the substrate. The nanoparticles may be selected from the group consisting of carbon fibers, glass fibers, polypropylene fibers, nylon fibers, polylactide fibers, and combinations thereof.
[0027] In some embodiments, filter medium also comprises the adhesive in the fibrous material, and this adhesive bonds nanoparticles on the fiber.This adhesive can comprise multiple conventional materials, comprises natural base material (for example starch, dextrin, guar gum etc.) or synthetic resin (for example EVA, PVA, PVOH, SBR, polyglycolide etc.).In some embodiments, substrate comprises its own adhesive composition.In these embodiments, can add or not add adhesive or bonding material on substrate.In such embodiment, substrate comprises biocomponent fiber, and one of them comprises the sheath that at least partially surrounds core.In some embodiments, core and sheath are not concentric, and in other embodiments, core and sheath are concentric.
[0028] Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic materials, acrylic, carbon, metals (e.g., alumina), polymers (e.g., nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefins, polyacetals, polyesters, cellulose ethers, polyalkylene sulfides, poly(arylene oxides), polysulfones, modified polysulfone polymers and polyvinyl alcohol, polyamides, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride, and any combination thereof.
[0029] The substrate fibers may be made by any method, including but not limited to air-laid, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, island-in-the-sea staple fibers or spunbond, segmented pie staple fibers or spunbond, etc. Contemplated fibers may have a variety of cross-sectional shapes, including but not limited to round, bean-shaped, dog-bone-shaped, trilobal-shaped, barbell-shaped, bow tie-shaped, star-shaped, Y-shaped, etc.
[0030] The fibers may be man-made or natural fibers. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfumaronitrile, polystyrene, styrene maleic anhydride, polymethylpentene, cycloolefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (e.g., P(VDF-TrFE)) or terpolymers (e.g., P(VDF-TrFE)) with PVDF. FE-CEF)), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonate, acrylic acid, styrenated acrylic acid, preoxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic or vinyl acetate, epoxy resin, acrylic multipolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof. Other conventional fiber materials are also contemplated.
[0031] In another aspect, a method of making a filter medium includes providing a fiber substrate, electrostatically charging the fibers, and dispersing nanoparticles into the substrate. The electrostatically charged fibers effectively capture submicron particles, at least during the initial use of the filter. The nanoparticles ensure that the filter remains highly efficient even after the electrostatic charge begins to decay over time. In addition, the bonding between the fibers and the nanoparticles can be enhanced by the electrostatic charge, which allows the nanoparticles to be dispersed throughout the filter medium at a certain depth.
[0032] The fibers in the substrate can be electrostatically charged using triboelectric methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. In certain embodiments, the method includes corona charging the fibers. In other embodiments, the method includes tribocharging the fibers.
[0033] In certain embodiments, the fibers are charged before the nanoparticles are dispersed into the substrate. In other embodiments, the nanoparticles are dispersed and captured within the substrate and then the fibers are electrostatically charged. In another embodiment, these processes may occur substantially simultaneously.
[0034] In certain embodiments, the method includes electrospinning the fibers. In other embodiments, the method includes needle punching the fibers and the nanoparticles together. The method may include carding the fibers. The method may include spunbonding the fibers. The method may include meltblowing the fibers.
[0035] In certain embodiments, the method includes dispersing nanoparticles onto a first surface of a substrate such that the nanoparticles penetrate at least the first surface of the substrate. The method may include isolating a single nanoparticle in a fluid, wherein the single nanoparticle has at least one dimension less than 1 micron.
[0036] The method can also include separating and / or isolating nanoparticles in a gaseous medium, such as air, helium, nitrogen, oxygen, carbon dioxide, etc., and then dispersing the nanoparticles into a substrate via an airflow, an aerosol, an evaporator, a spray, or other suitable delivery mechanism. Individual nanoparticles are separated and / or isolated in a gaseous medium, and then dispersed into a substrate or airflow so that the nanoparticles are more evenly distributed throughout the product. In addition, the nanoparticles can be dispersed or distributed into the product "at a certain depth".
[0037] The recitation herein of desirable objectives met by various embodiments of this specification is not meant to imply or suggest that any or all of these objectives are present as essential features, either individually or collectively, in the most general embodiment of this specification or in any of its more specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a side view of a nonwoven material having nanoparticles dispersed throughout a portion of the material;
[0039] Figure 2 is a side view of a nonwoven material having nanoparticles dispersed throughout the material;
[0040] Figure 3 is a side view of a nonwoven material having nanoparticles dispersed within the material in a gradient manner;
[0041] Figure 4 A double layer of filter media is shown;
[0042] Figures 5A-5C Biocomponent fibers incorporated into nonwoven materials are shown;
[0043] Figure 6 A pleated nonwoven filter media is shown;
[0044] Figure 7 A representative air filter is shown;
[0045] Figure 8 A gas filter having first and second support membrane layers and a filter medium is shown;
[0046] Fig.9A and 9B An apertured membrane used as a support membrane layer is shown;
[0047] Figures 10A-10E Various embodiments of open-pore films having nanoparticles incorporated into the film are shown;
[0048] Fig.11 A gas filter is shown;
[0049] Fig.12 A system for producing a nonwoven material within a substrate is schematically shown;
[0050] Fig.13 A system for converting nanofiber clusters into individual nanoparticles is schematically shown;
[0051] Figures 14A-14C Photographs of large nanofiber clusters, small nanofiber clusters, and single nanoparticles, respectively.
[0052] Fig.15 Shows Fig.13 The system's injectors;
[0053] Fig.16 Shows Fig.13 A reactor of the system;
[0054] Fig.17 Another embodiment of a system for converting nanofiber clusters into individual nanoparticles is shown;
[0055] Fig.18 A system for producing a double-layer nonwoven material is shown;
[0056] Fig.19 A nonwoven material having nanoparticles dispersed within the material at a certain depth is shown;
[0057] Fig. 20 A nonwoven material having nanoparticles dispersed within the material at a depth and a scrim layer covering the nanoparticles is shown;
[0058] Fig.21 A double-layer nonwoven material having nanoparticles dispersed on the inner surfaces of both layers is shown;
[0059] Fig. 22 An alternative embodiment of a system for producing a nonwoven material in a fluid stream is shown;
[0060] Fig.23A is a photograph of a nonwoven material without the use of an adhesive;
[0061] Fig. 23B is a photograph of a nonwoven material having an adhesive;
[0062] Fig.24Ais a photograph of a nonwoven material having nanoparticles dispersed throughout the material in the form of clumps or clusters; and
[0063] Fig. 24B is a photograph of a nonwoven material having nanoparticles substantially uniformly dispersed throughout the material. DETAILED DESCRIPTION
[0064] This specification and the accompanying drawings illustrate exemplary embodiments and should not be considered restrictive, and the claims (including equivalents) define the scope of this specification. Various mechanical, compositional, structural and operational changes can be made without departing from the spirit and scope of this specification and the claims (including equivalents). In some cases, well-known structures and techniques are not shown or described in detail to avoid confusing the description. The same numbers in two or more drawings represent the same or similar elements. In addition, whenever feasible, the elements and related aspects described in detail with reference to one embodiment can be included in other embodiments that do not specifically show or describe them. For example, if an element is described in detail with reference to one embodiment without describing the element with reference to a second embodiment, the element can still be included in the second embodiment. In addition, the description herein is for illustrative purposes only and does not necessarily reflect the actual shape, size or dimensions of the system or the components shown.
[0065] It should be noted that the singular forms "a," "an," and "the," as well as any singular use of any word as used in this specification and the appended claims, include plural referents unless expressly and unequivocally limited to one referent. The term "include," and its grammatical variations as used herein are intended to be non-limiting, such that the recitation of items in a list does not exclude other like items that can be substituted or added to the listed items.
[0066] Unless otherwise indicated, any numerical values are approximate, whether or not the term "about" or "approximately" is used. The materials, methods, and examples described herein are illustrative only and not limiting.
[0067] Nonwoven materials and products comprising nonwoven materials are provided, and the nonwoven materials include substrates, sheets, layers, films, apertured films, nets or other media, which include fibers and nanoparticles bonded to the fibers and incorporated into at least a portion of the substrate. The term "nanoparticle" means any particle having a size less than 1 micron on at least one axis or dimension. For example, fibers having a diameter or width less than 1 micron and a length greater than 1 micron are nanoparticles used herein.
[0068] In certain embodiments, each single nanoparticle can be a small particle with a size in the range of about 1 nanometer to about 1000 nanometers, preferably in the range of about 1 nanometer to about 650 nanometers. In the number size distribution, the particle size of at least half of the particles can be 100 nanometers or less. Most nanoparticles are usually composed of only a few hundred atoms. When the size of the nanoparticle approaches the atomic scale, the material properties will change. This is because the surface area to volume ratio increases, which causes the surface atoms of the material to dominate the performance of the material. Due to its very small size, when compared with bulk materials such as powders, plates, sheets or larger fibers, nanoparticles have a very large surface area to volume ratio. This characteristic makes nanoparticles have unexpected optical, physical and chemical properties because they are small enough to limit their electrons and produce quantum effects.
[0069] In some embodiments, the nanoparticles include nanofibers having at least one dimension (i.e., diameter, width, height, etc., depending on the cross-sectional shape of the fiber) less than 1 micron. The nanofibers may have continuous lengths, or the nanofibers may have discrete lengths, such as 1 to 100,000 microns, preferably about 100 to 10,000 microns.
[0070] Nonwoven substrates described herein may include interwoven, interlocked or bonded single fibers or wire structures. Nonwoven fabrics may include sheets or web structures bonded together by mechanical, thermal or chemically entangled fibers or filaments (and by perforated films). They may be substantially flat porous sheets directly made of independent fibers or molten plastics or plastic films. Suitable nonwoven examples include, but are not limited to, fibers, layers or webs processed by meltblowing, spunbonding or spunlace, thermal bonding, bonding combing, air-laid, wet-laid, co-molding, acupuncture, stitching, hydraulic entanglement, etc.
[0071] In certain embodiments, the substrate may comprise knitted and / or woven materials. Knitted materials may include any knitting pattern suitable for a desired application. Knitted materials suitable for filter applications include weft knitting, warp knitting, knitted meshes, compressed knitted meshes, etc. Woven materials suitable for filtration applications include textile filter media, such as monofilament fabrics, multifilament fabrics, nylon nets, polyester nets, polypropylene nets, etc. Woven textiles may be used, for example, for mesh filter press filter cloths, woven filter pads and other die-cuts, centrifuge filter bags, liquid filter bags, dust collector filter bags, bed dryer filter bags, rotary drum filters, filter belts, leaf filters, roll media, etc.
[0072] In some embodiments, the nonwoven material can include a structure comprising chopped fibers and / or filaments that are mixed or tangled. As used herein, chopped fibers refer to fibers of limited length. Filaments used herein refer to fibers with substantially continuous length. In some embodiments, substrates can include chopped coarse fibers, microfibers and / or fine fibers. "Fine fibers" as used herein refer to fibers with a diameter less than 1 micron, "coarse fibers" refer to fibers with a diameter greater than 10 microns, and microfibers refer to synthetic fibers with a diameter less than 10 microns.
[0073] In certain embodiments, nanoparticles are dispersed in substrate "at a certain depth". As used herein, the term "at a certain depth" means that nanoparticles are dispersed across the first surface of substrate so that at least some nanoparticles are arranged between the first and second relative surfaces in the substrate or the internal structure of the medium. In certain embodiments, nanoparticles are dispersed throughout the substantially entire medium from the first surface to the relative second surface. In other embodiments, nanoparticles are dispersed in a portion of medium from the first surface to the position between the first and second surfaces. In some embodiments, nanoparticles are spatially three-dimensionally distributed relative to supporting fibers, which can increase the fiber surface area and microvolume in the nonwoven material. Three-dimensional distribution can also prevent the complete blocking of a specific part of the nonwoven material, which is particularly useful in filter media because it allows fluids (such as air and other gases) to pass through the filter, thereby reducing the total pressure drop on the filter.
[0074] In other embodiments, the thickness of nanoparticles across substrate is arranged with density gradient, so that the density of nanoparticles arranged near a surface is higher than the relative surface, or compared with the middle part of substrate, the density of nanoparticles arranged on the surface is higher. The density gradient shown can be substantially linear, it can be reduced in the form of a series of discrete steps, or gradient can be random (that is, the reduction of density is not usually linear or step-like). This density gradient provides many favorable features (as described below) for some applications (such as filters). Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic material, acrylic acid, carbon, metal (such as aluminum oxide), polymer (such as nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefin, polyacetal, polyester, cellulose ether, polyalkylene sulfide, poly (arylene oxide), polysulfone, modified polysulfone polymer and polyvinyl alcohol, polyamide, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride and any combination thereof.
[0075] In some embodiments, nanoparticles can be made into bicomponent segmented cake-like and island-like. Then, long filaments are stretched to obtain submicron filaments. Continuous filament nanofibers are cut according to desired length (preferably about 100 to about 10000 microns). In some embodiments, nanoparticles are absorbents and adsorbents. In some embodiments, nanoparticles are activated carbon fibers or activated carbon powder. In some embodiments, nanoparticles are catalytic particles or catalytic fibers. In some embodiments, nanoparticles can be obtained by feeding submicron fiber nonwoven materials into pulverizer or crusher or trimmer, in which the bonded nonwoven material enters and short-cut fibers come out. For example, low weight biocomponent melt-blown or nano melt-blown fabrics can be sent into pulverizer, thereby obtaining submicron nanoparticles.
[0076] In some embodiments, different nanoparticles can be mixed. For example, nanofibers and nanobeads can be mixed. Two different nanofibers with different melting points can also be mixed so that the nanoparticles with a lower melting point can serve as a binder for the nanofibers with a higher melting point. Nanoparticles of different diameters and different lengths can also be mixed.
[0077] In some embodiments, the nanoparticles are selected from environmentally sustainable raw materials. The nanoparticles may include biosoluble glass nanofibers, biodegradable nanoparticles, compostable nanoparticles, or recyclable compositions.
[0078] Different types of nanoparticles can be combined. Some nanoparticles can be functional nanoparticles. For example, functional nanoparticles can contain activated carbon and / or antimicrobial materials deposited on and / or attached to the fibers in the nonwoven material. This can improve the gas absorption efficiency and bactericidal effect of the fiber. In addition, nonwoven products in which microfibers of glass and carbon nanoparticles are deposited can provide filtering and deodorizing functions as filter media.
[0079] In some embodiments, nanoparticles are attached to the fiber by mechanical entanglement. As discussed in more detail below, this mechanical bonding can be assisted by adhesives or bonding agents. In some embodiments, nanoparticles are not curled (that is, they do not include the obvious wavy, curved, curled, coiled sawtooth or similar shapes relevant to the nanoparticles in the relaxed state). In other embodiments, nanoparticles can have a curled body structure with discrete lengths. For example, when these curled nanofibers with discrete lengths are attached to the fiber, they tangle with each other, and are firmly attached to the fiber, attached to the fiber and attached to the fiber around, thereby forming modified fibers. In other embodiments, the attachment of nanofibers to microfibers is to attract and / or van der Waals forces to realize by the static charge between fiber and the nanoparticles.
[0080] Also provided are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, plate filters, etc., which contain nanoparticles dispersed in the filter media at a certain depth. In some embodiments, the filter includes one or more support layers bonded to the filter media. The support layer and / or the filter media may include nanoparticles dispersed in the layer at a certain depth. In some embodiments, a polymer layer, a membrane layer or a membrane is provided, which includes one or more holes for gas or liquid to flow through, and the nanoparticles are arranged in the polymer layer at a certain depth. In other embodiments, the nonwoven material includes a flexible surface layer for finger bandage pads, masks, etc.
[0081] Provided herein are systems, devices and methods for producing nonwoven materials and products (e.g., gas filters) comprising nonwoven materials. Also provided are systems and methods for isolating single nanoparticles in a gaseous medium, such as air, helium, nitrogen, oxygen, carbon dioxide, etc. (rather than liquid), and the nanoparticles can be dispersed into another product, film, layer or substrate by airflow, aerosol, evaporator, spray or other suitable delivery mechanism.
[0082] Although the following description is mainly directed to nonwoven materials and filter media, it should be understood that the devices and methods disclosed herein can be easily adapted to various other applications. For example, the nonwoven materials disclosed herein can be used for household cleaning products, roofing and floor products, automotive interiors and headliners, reusable bags, wall coverings, filtration devices, insulation materials, etc. In addition, the single nanoparticles isolated and generated in the methods described herein can be used for various coatings, composite materials and / or additives, for example, polymers, food packaging, flame retardants, fuel cells, batteries, capacitors, nanoceramics, lamps, material manufacturing, production methods, reinforcements of composite materials, cements and other materials, medical diagnostic applications, medical treatment devices or therapies, tissue engineering (such as scaffolds for bone or tissue repair), drinking water, industrial process fluids, food and beverage products, drugs and biological preparations, tissue imaging, medical treatment delivery, environmental applications (such as biodegradable compounds), etc. A more complete description of articles that may incorporate nanoparticles may be found in commonly assigned, co-pending U.S. Provisional Patent Applications Nos. 63 / 328,970, 63 / 328,959, 63 / 328,983, 63 / 328,998, 63 / 329,009, 63 / 329,018, 63 / 329,137, 63 / 329,146, 63 / 329,155, 63 / 329,158, 63 / 329,161, and 63 / 329,162, all filed on April 8, 2022, the entire disclosures of which are incorporated herein in their entirety for all purposes.
[0083] Figure 1 A nonwoven material or substrate 10 comprising a plurality of fibers 12 and nanoparticles 14 is shown. The substrate 10 has a first surface 16 and a second surface 18 opposite to the first surface 16, and defines a width or thickness between the first surface 16 and the second surface 18. The nanoparticles 14 have been deposited into the substrate through the first surface 16. As shown, the nanoparticles 14 penetrate into the substrate 10 of a certain depth between the first surface 16 and the second surface 18 through the first surface 16. In some embodiments, the nanoparticles 14 penetrate from the first surface to at least 25% of the width or thickness between the first surface 16 and the second surface 18, or more preferably penetrate to at least about 50% of the thickness. In other embodiments, the nanoparticles 14 substantially penetrate throughout the substrate 10 from the first surface 16 to the second surface 18.
[0084] Nanoparticles 14 preferably include individual nanoparticles (e.g., nanoparticles that have been broken up, separated, and isolated from one another prior to being dispersed into substrate 10. Fig. 24BAs shown in FIG. 1 , the nanoparticles 14 are not present in the nonwoven product in the form of a layer and do not have obvious nanofiber agglomerates or bundles (such as Fig.24A As shown). This allows the nanoparticles to be more dispersed throughout the substrate, which provides a more efficient filtration capability to filter out pollutants in certain applications (e.g., gas filters). In addition, this allows the nanoparticles in the nonwoven material to have a greater area density (in grams per square meter (gsm)) or "addition amount" within the material. The term "addition amount" is used herein to refer to the area density (gsm) of a material, fiber, or particle in a thin layer, sheet, or film of material.
[0085] In certain embodiments, the nanoparticles can include an addition of about 0.1 g / m2 to about 20 g / m2, preferably at least about 2.0 g / m2. Specific addition or surface density may depend on application. For example, the applicant has found that higher surface density or addition can improve the efficiency of nonwoven materials in filtering out pollutants. Therefore, specific nanoparticle addition may depend on the expected efficiency of the filter medium.
[0086] Figure 2 A nonwoven material or substrate 20 is shown that includes a plurality of fibers 12 and nanoparticles 14. As shown, the nanoparticles 14 penetrate the entire width of the substrate 20 from the first surface 16 to the second surface 18. In certain embodiments, the nanoparticles 14 are substantially dispersed throughout the fibers 12 of the substrate, such as Figure 2 In some embodiments, the density of nanoparticles located at the first surface 16 differs from the density of nanoparticles dispersed in the central portion of the substrate 20 between the surfaces 16 and 18 by less than 50%. In some embodiments, the difference is less than 25%, preferably less than 10%. In some embodiments, the amount or number of individual nanoparticles dispersed in the central portion of the substrate 20 is at least about 50%, preferably at least about 75%, and more preferably at least about 90% of the amount of individual nanoparticles dispersed at or near the first surface 16.
[0087] In other embodiments, the nanoparticles 14 are arranged in a density gradient from the first surface 16 to the second surface 18. For example, Figure 3A substrate 30 is shown in which the nanoparticles 14 form a density gradient, with the density of the nanoparticles 14 disposed near the first surface 16 being higher than the density of the nanoparticles 14 near the second surface 18. In certain embodiments, the difference between the density of the nanoparticles located at the first surface 16 and the density of the nanoparticles dispersed at the second surface 18 is greater than about 75%. In some embodiments, the difference is greater than 50%. In some embodiments, the difference is greater than 25%. In certain embodiments, the amount or number of individual nanoparticles dispersed at or near the second surface 18 is less than about 50%, preferably less than about 25%, and more preferably less than about 10% of the amount of individual nanoparticles dispersed at or near the first surface 16.
[0088] Figure 3 The density gradient shown is substantially linear from the first surface 16 to the second surface 18. Alternatively, the density of the nanoparticles 14 can decrease from the first surface 16 to the second surface 18 in a series of discrete steps, or the gradient can be random (i.e., the decrease in density is generally not linear or step-like).
[0089] In other embodiments, nanoparticles may be added to the substrate from the first surface 16 and the second surface 18. In these embodiments, the surface density or "addition amount" at the first surface 16 and the second surface 18 may be substantially equal to each other, or they may be different depending on the application. In these embodiments, the surface density or "addition amount" in the middle of the substrate is lower than the surface density or "addition amount" at the surfaces 16, 18. For example, the surface density in the middle of the substrate may be about 75% of the surface density at the surfaces 16, 18, or may be about 50%, 40%, or 25%.
[0090] The distribution of nanoparticles across the thickness of the nonwoven material can be measured, for example, using imaging techniques. An enlarged view of the nonwoven product is taken using an electron microscope or other technique at a horizontal cross section of the product in the middle of the product thickness, which can be compared to an image taken at the upper or lower surface of the product, or all three images can be compared to determine the extent of variation in the amount of deposited nanoparticles. Computer image analysis processing can be used. For example, in Figure 3In the present invention, a cross section can be taken at line AA, and a cross section can be taken at line BB. A top view of each cross section can be obtained by an electron microscope, a scanning electron microscope, and other microscopes. For example, a top view of a cross section obtained at section AA can be compared with a top view obtained at section BB. The number of microfibers, the number of nanoparticles, or both in samples of the same two-dimensional size can be evaluated and compared. In addition, imaging techniques can be used on three-dimensional samples. These techniques can be used to evaluate the orientation and other characteristics of the fibers. These techniques can be used to determine that the nanoparticles have been deposited into a certain depth of the substrate, have been substantially deposited in a large part of the substrate, substantially in the entire depth of the substrate, or in a certain depth of the substrate.
[0091] The contemplated substrate fibers may be made by any method including, but not limited to, air laying, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, islands in the sea staple fibers or spunbond, segmented cake staple fibers or spunbond, and the like. Such methods are described in U.S. Pat. Nos. 4,406,950, 6,338,814, 6,616,435, 6,861,142, 7,252,493, 7,300,272, 7,309,430, 7,422,071, 7,431,869, 7,504,348, 7,774,077, 9,522,357, 9,993,761, and U.S. Patent Publication No. 2009 / 266,759, the entire disclosures of which are incorporated herein by reference for all purposes.
[0092] Contemplated fibers may have a variety of cross-sectional shapes, including but not limited to round, kidney bean, dog bone, trilobal, barbell, bow tie, star, Y, etc. These and / or other conventional shapes may be used in conjunction with embodiments to achieve desired performance characteristics. The fibers in the substrate are held connected to each other by thermal bonding, chemical bonding, interentanglement, use of a binder (e.g., adhesive), etc.
[0093] The fibers may be man-made or natural fibers. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfumaronitrile, polystyrene, styrene maleic anhydride, polymethylpentene, cycloolefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (e.g., P(VDF-TrFE)) or terpolymers (e.g., P(VDF-T rFE-CEF)), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, polymethyl methacrylate, polyoxymethylene, polysulfonate, acrylic acid, styrenated acrylic acid, preoxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic acid or vinyl acetate, epoxy resin, acrylic multipolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof. Other conventional fiber materials are also contemplated.
[0094] The fibers can include fibers of different sizes, with the diameters of the fibers typically ranging from about 1 micron to about 1000 microns and lengths ranging from about 1 / 2 inch to 3 inches. The fibers can be configured as a gradient density media, wherein the pore size decreases from the upper surface (upstream) to the lower surface (downstream) of the filter to improve capture efficiency and dust collection capabilities. This configuration also allows different amounts of nanoparticles to be dispersed into the filter media at different depths. For example, the upstream side of the filter media can have the largest fiber size to allow more void space and a greater density of nanoparticles, while the downstream side of the filter media has smaller sized fibers to provide a lower density of nanoparticles. Alternatively, the structure can be reversed to provide a higher density of nanoparticles in the downstream portion of the filter media.
[0095] The fibers in the medium can be kept connected to other fibers by thermal bonding, chemical bonding or mutual entanglement. Bicomponent fibers can be used, especially in the case of mechanical filtration, and these fibers are formed by extruding two polymers from the same spinneret, and both polymers are contained in the same filament. Suitable materials for bicomponent fibers include, but are not limited to, polypropylene (PP) / polyethylene (PE), polyethylene terephthalate (PET) / polypropylene (PP), etc.
[0096] In some embodiments, the substrate may comprise a "high loft" nonwoven material comprising spunbond or through-air bonded carded nonwoven fibers. As used herein, the term "high loft" means that the volume of the void space is greater than the volume of the total solids. In through-air bonded carded nonwoven fibers, the loft of the substrate can be controlled in various ways known to those skilled in the art. For example, the loft can be increased by applying less compressive force to the medium during the bonding process. In another example, the high loft nonwoven material can be produced with fibers having a greater thickness (e.g., a thickness greater than 3 denier, such as 5 denier or greater, 6 denier or greater) (discussed in more detail below). In other embodiments, the loft can be increased by using biocomponent fibers of different concentricities, such as Figure 5C shown and discussed in more detail below.
[0097] In certain embodiments, the fiber may include a silicon-based coating to improve the efficiency of the filter medium in capturing pollutants (particularly pollutants within the E2 and E3 particle groups). The silicon-based coating may include a reactive silicon coarse emulsion. Silicon emulsions may include, for example, dimethyl silicone emulsions, amino-type silicone emulsions, organofunctional silicone emulsions, resin-type silicone emulsions, film-forming silicone emulsions, and the like. In one embodiment, the reactive silicon coarse emulsion comprises amino-functional polydimethylsiloxane and / or polyethylene glycol monotridecyl ether. Suitable silicon coatings are described in the co-assigned U.S. Provisional Patent Application Serial No. 63 / 406,686 filed on September 14, 2022, the complete disclosure of which is incorporated herein by reference. The filter medium may include a charge additive to change the friction charge of the fiber and increase the stability and / or duration of the friction charge in the filter. This improves the overall filtration efficiency of the filter without compromising other important properties of the filter, such as life, dust holding capacity, and pressure drop or air flow through the filter. Charge additives suitable for tribocharging are described in commonly assigned Provisional Patent Application No. 63 / 410,731, filed on September 28, 2022, the entire disclosure of which is incorporated herein by reference for all purposes.
[0098] Fiber can have the thickness suitable for application.In some embodiments, fiber has at least one size in the range of about 1 micron to about 10000 microns or in the range of about 1 micron to about 1000 microns or in the range of about 10 to 100 microns.The thickness of fiber can also be measured by denier, and denier is the measurement unit of the linear mass density of fiber.In some embodiments, fiber can have the linear density of about 1 denier to about 10 deniers.Nanoparticle is the fiber with at least one size in the range of about 1 nanometer to about 1000 nanometers or in the range of about 1 nanometer to about 100 nanometers.The size of above-mentioned fiber and nanoparticle can be diameter or width, and this depends on the shape of fiber or nanoparticle.
[0099] For gas filters (eg, pleated or non-pleated air filters), the linear density of the fibers may range from about 1 denier to about 10 denier. The filter media may contain fibers having the same or different linear densities.
[0100] The fibers in air filters typically have a linear density of about 3 deniers or less to ensure that the fibers are small enough to capture pollutants that pass through the filter. Applicants have surprisingly discovered that by using nanoparticles dispersed in the filter media, the fibers can have a greater linear density, such as greater than 3 deniers. This is because the nanoparticles provide significant filtering capabilities. In some cases, the fibers can have a linear density greater than 3 deniers, 5 deniers or greater, 6 deniers or greater, or up to 7-10 deniers.
[0101] Applicants have also discovered that in some applications, fibers having a greater linear density (e.g., greater than about 3 denier) than fibers used in conventional filters provide more open space or pores in the filter media, which allows a greater density of nanoparticles to be dispersed therein. Although this may be counter-intuitive to one skilled in the art, Applicants have discovered that incorporating nanoparticles into fibers having a greater linear density actually improves the overall efficiency of the filter.
[0102] In some embodiments, the filter medium may include at least two different fiber thicknesses or linear densities to provide at least two different filter layers in the same filter medium. For example, in some cases, a portion of the filter medium may include fibers having a linear density greater than 3 deniers, such as 5 deniers or greater, or 6 deniers or greater. Other portions of the filter medium may include fibers having a more standard linear density of 3 deniers or less. This double-layer filter medium produces a first filter portion and a second filter portion, the first filter portion primarily utilizing nanoparticles with a high density within the larger thickness fiber to filter pollutants, the second filter portion primarily utilizing fibers with a lower linear density to filter pollutants, although both portions may include nanoparticles dispersed throughout the fiber. In some embodiments, the filter medium may include three or more separate portions or layers, each portion having a different denier fiber range.
[0103] Figure 4 A dual-layer filter medium is shown, which includes a first substrate 40 having a first surface 42 and a second surface 44 opposite the first surface; and a second substrate 50 having a first surface 52 and a second surface 54 opposite the first surface. The second surface 44 of the substrate 40 is bonded to the second surface 54 of the first substrate in any manner known to those skilled in the art. The first substrate 40 includes fibers 46 of a relatively small linear density, such as about 3 denier or less. The second substrate 50 includes fibers 56 of a relatively large linear density, such as about 3 denier or greater, such as 5 denier, 6 denier or greater. The second substrate 50 also includes individual nanoparticles 58 dispersed throughout the fibers 56 and bonded to the fibers 56 and / or retained by the second substrate 50. The first substrate 40 may or may not include nanoparticles.
[0104] The first substrate 40 is configured to filter pollutants primarily using fibers 46, but as previously described, the first substrate 40 may also include nanoparticles. The second substrate 50 is configured to filter pollutants using fibers 56 and nanoparticles 58.
[0105] In some embodiments, the substrate may include additives such as antimicrobial and / or antiviral compositions, such as silver, zinc, copper, silicone, tributyltin, organic compounds containing chlorine, bromine, or fluorine compounds.
[0106] The fibers may include biocomponent fibers that include two or more different fibers bonded to each other. The fibers may comprise the same material or different materials.
[0107] Figures 5A-5C Various examples of biocomponent fibers that can be used with the nonwoven materials disclosed herein are shown. Figure 5AA fiber 60 is shown having a core fiber 62 and a surrounding sheath fiber 64. In this embodiment, the core 62 is substantially concentric with the sheath. Figure 5B A biocomponent fiber 70 is shown having a first fiber 72 and a second fiber 74 arranged side by side with one another. Figure 5C A biocomponent fiber 80 is shown having a core fiber 82 and a sheath fiber 84. In this embodiment, the core 82 is not concentric with respect to the longitudinal axis of the sheath 84, which increases the overall loft of the biocomponent fiber. Of course, other configurations are possible. For example, the core can include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Alternatively, the fiber can include multiple cores, or can be divided into three, four, or more quadrants.
[0108] In some embodiments, nonwoven material (that is, fiber and / or nanoparticle) can be electrostatically charged, which for example makes pollutants be captured by mechanical and electrostatic filtration. The bonding between fiber and nanoparticle can also be enhanced by electrostatically charging nanoparticle, fiber or both. For example, in some embodiments, fiber is electrostatically charged, thereby nanoparticle can be utilized to realize mechanical filtration, and electrostatic filtration can be realized by electret substrate simultaneously. Electrostatic or electret substrate can be the high-loft triboelectric filter medium made by combing and acupuncture. In one embodiment, preferably before acupuncture, nanoparticle is deposited in substrate, and then electrostatic fiber and nanoparticle acupuncture are together.
[0109] The substrate, nanoparticles, or both may be electrostatically charged using triboelectric methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. Corona charging is suitable for charging single polymer fibers or fiber blends or fabrics. Tribocharging may be suitable for charging fibers with different electronegativity. Electrostatic fiber spinning combines the charging of polymers and the spinning of fibers into a one-step process. Suitable methods for triboelectric charging are described in U.S. Provisional Patent Application No. 63 / 410,729, filed on September 28, 2022, and U.S. Patent No. 9,074,301, both of which are jointly assigned, the entire disclosures of which are incorporated herein by reference for all purposes.
[0110] Nanoparticles can be selected to have different triboelectric properties relative to the fibers in order to use the triboelectric effect to enhance particle removal. With this approach, the resulting nanoparticles are formed in an electric field and are less susceptible to contamination by chemicals that can mitigate the triboelectric effect. Nanoparticles can also be used with different adsorption properties or surface charge characteristics than the macrofibers, such as for oil or water filtration. This difference can be used to enhance or create local electric field gradients within the filter media to enhance particle removal. The nanoparticles and macrofibers can have different wetting properties.
[0111] The nonwoven material may include a binder or adhesive material, such as an adhesive or binder, to promote bonding between fibers and / or retention of nanoparticles in the substrate, so that the nanoparticles can adhere to the fibers, or otherwise be retained in the substrate by the fibers to form a stable matrix. The binder or adhesive material is preferably present in a relatively small amount to bond a single nanoparticle to the fibers of the entire substrate.
[0112] The adhesive may comprise a variety of conventional materials, including natural materials (e.g., starch, dextrin, guar gum, etc.) or synthetic resins (e.g., EVA, PVA, PVOH, SBR, polyglycolide, etc.) In certain embodiments, a solvent-based adhesive is used, wherein bonding occurs when the solvent evaporates.
[0113] In a preferred embodiment, the adhesive or adhesive material comprises dextrin. In another embodiment, the adhesive comprises a combination of various substances, such as water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzenesulfonate, laurylamine oxide and ammonium hydroxide. In yet another embodiment, the adhesive comprises at least PVOH. The adhesive can be a solution, an emulsion, a suspension, a hot melt, a curable material, a pure material and / or a combination thereof.
[0114] In some embodiments, adhesive resin is used, and adhesive resin can be cross-linked after adhesive is applied to substrate. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when solvent evaporates in adhesive formulation or heat activation in drying process. For some adhesives, crosslinking can be realized by electromagnetic radiation (including but not limited to RF, UV or electron beam) of high energy wavelength. The amount of adhesive can be controlled by adjusting the nozzle size of sprayer 140 or the flow rate of control adhesive composition. Adhesive can be applied using nozzle, dip coating or other methods. In some embodiments, adhesive or bonding material can include surfactant, to reduce the surface or interfacial tension of adhesive, thereby improve its dispersion and wetting properties, and make adhesive more easily penetrate into substrate of certain depth. Suitable surfactants for use with the adhesives disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzene sulfonate, sodium dodecylbenzene sulfonate wetting agent, docusate (sodium dioctyl sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), and the like.
[0115] In some embodiments, the substrate comprises its own adhesive composition. In these embodiments, an adhesive or bonding material may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers, one of the components comprising a sheath at least partially surrounding a core (see Figure 5A and 5C ).
[0116] The sheath may comprise a material that is bonded to the nanoparticles. For example, the sheath may comprise a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step (discussed below), the sheath portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously.
[0117] Fig.23A is a magnified image of a nonwoven product having nanoparticles deposited therein without the use of a binder material. Fig. 23B is an enlarged image of a nonwoven product in which a binder material of dextrin and water is used to adhere nanoparticles to fibers. As shown, with the use of a binder, the nanoparticles are more uniformly adhered to the fibers.
[0118] exist Fig.23A and 23B In the examples of , a substrate having bicomponent microfibers is used, the inner portion of the bicomponent microfibers being polyester and the outer portion being high density polyethylene ("HDPE"). Fig.23A A microfiber nonwoven product having a bicomponent microfiber substrate is shown, in which a layer of biosoluble glass nanofibers is deposited only on the surface of the substrate, and electrostatic forces are relied upon to retain the nanofibers. Fig.23A Agglomeration of nanofibers can be seen in the substrate, and the retention of nanofibers is poor. The substrate can be produced using meltblowing, spunbonding, or other methods described herein.
[0119] exist Fig. 23B In the example, an adhesive material is used. A mixture of dextrin and water is used to spray the substrate, and nanoparticles are applied to the substrate, wherein the uniformity of the nanofibers is higher and the retention rate is greater. In other examples, any adhesive material disclosed herein can be used. In addition, the nanoparticles of biosoluble glass have been deposited into a substrate at a certain depth. In this example, the bicomponent microfiber substrate itself has a MERV rating of 4 to 10, which can be achieved using any method described herein. In one example, due to the deposition of nanoparticles into a substrate at a certain depth and with an electrostatic charge, a microfiber substrate with an initial MERV of 8 has been used to produce a nonwoven product with a MERV of 13. In another example, a microfiber substrate with an initial MERV of 6 has been used to produce a nonwoven product with a MERV of 15. The substrate is provided on a roll, and in a roll-to-roll continuous process, as any process and method described herein, the nonwoven product can be produced on a commercial scale. In an example, the roll-to-roll process runs at a speed of 30 feet per minute.
[0120] In certain embodiments, the nonwoven materials discussed herein can be used as part of a filtration device that captures or absorbs pollutants, such as a liquid filter, a gas filter for home and commercial air filtration, a surgical or other mask, etc. The filtration device can be a mechanical filter, an adsorption filter, a barrier filter, an ion exchange filter, a reverse osmosis filter, a surface filter, a depth filter, etc., and can be designed to remove many different types of pollutants from air, water, etc.
[0121] In one such embodiment, nonwoven material is incorporated into an air filter for removing particles and pollutants from the air, such as HEPA filter (i.e., pleated mechanical air filter), UV filter, electrostatic filter, washable filter, media filter, glass fiber filter, pleated or non-pleated air filter, activated carbon filter, bag filter, V-bank compact filter, filter sheet, flat cell filter, filter cartridge, etc. Nonwoven material can comprise the filter medium of air filter, and can be supported by support layer, scrim layer, or can be included in other layers or materials. Applicant has found that, as discussed herein, nanoparticle depth is incorporated into nonwoven material and significantly improves the efficiency of air filter, without compromising other factors, such as pressure drop (i.e., air flow) through filter. In addition, these materials increase overall dust holding capacity, thereby extending the life of filter, particularly compared with filters that only or mainly rely on electrostatic effect to improve efficiency. Conventional home and commercial air filters such as HEPA filters are usually rated according to the ability of filter to capture about 0.3 to 10 micron particles. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is developed by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher numbers indicating greater efficiency in capturing a particular type of particle. Conventional mechanical air filters typically report a MERV rating of around 8 for nonwoven filter materials.
[0122] Air filters are usually rated based on their initial efficiency (i.e., the efficiency of the air filter before use) and their efficiency over time and use. The latter efficiency is usually tested through a conditioning procedure, see Appendix J of ASHRAE Standard 52.2.
[0123] The air filters provided herein have an initial MERV rating of greater than about 10 and a pressure drop of less than about 0.5 inches of water column. In some cases, the initial MERV rating is about 11 and the pressure drop is equal to or less than about 0.17 inches of water column, or the initial MERV rating is about 13 and the pressure drop is equal to or less than about 0.36 inches of water column, or the initial MERV rating is about 14 and the pressure drop is equal to or less than about 0.5 inches of water column.
[0124] The gas filters provided herein have a MERV rating of 10 or higher after conditioning in accordance with ASHRAE Standard 52.2, Appendix J. In some embodiments, the MERV rating is 13 or higher after conditioning the gas filter using ASHRAE Standard 52.2, ISO Standard 16890, or any other acceptable standard in the industry.
[0125] The MERV rating of the nonwoven filter media discussed herein will vary depending on many factors, including the type and size of fibers used in the filter media, the density of individual nanoparticles in the filter media, the width of the filter media, the number and size of pleats (if any), etc. The MERV rating can be measured for nonwoven product sheets as well as nonwoven products formed into pleated filter media, and the pressure drop for each product can be different. Likewise, the pressure drop across the filter media also depends on many factors, including those mentioned above.
[0126] One factor that affects the MERV rating and pressure drop is the density or amount of addition of the nanoparticles within the substrate relative to the density of the fibers within the substrate. Applicants have found that the lower the ratio between the substrate density and the nanoparticle density, the higher the MERV rating of the filter and the higher the pressure drop. In certain embodiments, the filter media described herein have a nanoparticle surface density of about 0.1 g / m2 to about 20 g / m2, preferably at least about 2 g / m2.
[0127] In some cases, the density of the nanoparticles will also depend on the density of the actual filter media (i.e., the density of the coarse fibers). As discussed in more detail below with reference to Table 2 below, a density ratio (substrate gsm divided by added nanoparticle gsm) of about 67 results in a pressure drop of about 0.14 inches of water column and an initial MERV rating of 10. A density ratio of about 33.4 increases the MERV rating to 10, but only results in an increase in pressure drop to about 0.17. A density ratio of about 22.3 increases the initial MERV rating to about 12, with a pressure drop of about 0.24 inches of water column.
[0128] Thus, the efficiency or MERV rating of the filter can be improved as the amount of nanoparticles added increases. In particular, Applicants have found that, for example, at an addition of at least 2 g / m2, a filter with a MERV rating of about 10 can be achieved. Additions of 4 or 6 g / m2 provide filters with MERV ratings of about 12 and 13, respectively. Additions of 10 g / m2 or more produce filters with a MERV rating of 15 or more.
[0129] Applicants have also discovered that including fibers with greater thickness or linear density results in larger pore sizes, resulting in greater pore volume, thereby allowing for a higher density of nanoparticles within the substrate. This results in higher MERV ratings and pressure drops (as discussed below with reference to Table 2). For example, Applicants have been able to make air filters with a MERV rating of 14 and a pressure drop of 0.5 inches of water column using 5 denier biocomponent fibers. Similarly, Applicants were able to make filters with a MERV rating of 13 and a pressure drop of only about 0.29 inches of water column using 5 denier biocomponent fibers.
[0130] Figure 6 An example of a pleated filter media 90 is shown in FIG. Depending on the application, the filter 90 may include about 0 to 10 pleats per inch. The filter media may be mounted in a cardboard or metal frame and used as an easily replaceable filter product ( Figure 7 ). As shown, a gas filter 94 is produced using the nonwoven materials described herein. As shown, the filter 94 includes a pleated nonwoven filter medium 96 and a support layer 98 that provides rigidity and structure to the filter medium 96.
[0131] Fig.11 A gas filter 109 made of a nonwoven material as described herein is shown. The gas filter 109 comprises a nonwoven substrate having fibers and nanoparticles dispersed in a certain depth of the substrate. The substrate is subsequently rolled into a cylindrical, conical or other suitable shape and can be used in applications such as gas turbine and compressor intake filters, plate filters, etc.
[0132] Other types of filters that can be developed using the nonwoven materials disclosed herein include conical filter cartridges, square end cap filter cartridges, bag filters, V-bank compact filters, plate filters, flat unit filters, pleated or non-pleated bag filter cartridges, etc. The nonwoven products disclosed herein can be used for medical masks or other medical applications, such as filter cartridges in respirators. Medical masks are intended to protect medical staff and / or patients from microorganisms and other substances. For example, medical masks can block bacteria (e.g., which can be about 3 microns in size) and viruses (e.g., which can be about 0.1 microns in size). The mask is made of multi-layer nonwoven materials and has ear loops, laces or other structures for attaching the mask to the face of the person. Metal wire can be incorporated into at least the upper portion of the mask so that at least the portion fits the face of the person. The mask can include a rigid polymer structure for fixing the multi-layer nonwoven material in front of the face of the person. In one example, the mask has three layers. The outer and inner layers contain nonwoven materials (e.g., spunbonded polypropylene) that provide air permeability, but any material mentioned herein can also be used. The middle layer is located between the inner layer and the outer layer and comprises a microfiber substrate having nanoparticles deposited into the substrate to a depth to provide an initial MERV greater than 8, preferably greater than 10 MERV, and more preferably 13 or greater MERV. The pressure drop through the mask is 3 to 6 mm water column, and for breathability, 4 mm water column is more preferred. The efficiency of the mask is expected to be about 95%. Other examples of masks have four or more layers. Multiple layers of nonwoven products can be combined into a single mask.
[0133] In certain embodiments, the nonwoven material may be included in a film or layer that includes holes, pores, or perforations. The holes may be embossed into a pattern (e.g., circles, diamonds, hexagons, rectangles, triangles, rectangles, etc.) and then stretched until holes are formed in the thinned areas produced by the embossing. Such open-cell substrates may be formed from a variety of polymers (e.g., polypropylene, polyethylene, high-density polyethylene ("HDPE"), etc.). The polymer layer may, for example, comprise an extruded film. Open-cell films are commercially available and are available as The substrate is provided in the form of a roll and the nanofibers are deposited into the substrate in a roll-to-roll process. Figures 10A-10E An example of an open-cell membrane formed using the methods described herein is shown. In other embodiments, a gas filter comprises a filter medium and a substantially rigid support layer bonded to the filter medium. The support layer comprises fibers and individual nanoparticles dispersed at a depth within the layer. The nanoparticles are configured to filter contaminants that pass through the support layer.
[0134] refer to Figure 8, the composite filter member 814 includes an internal filter substrate 812 and one or more filter support members or membrane layers 810. The support member 810 can be formed by an extruded sheet of a polymer, such as a polypropylene film, a high-density polyethylene film, a polylactic acid film, or a thermoplastic polymer material, such as an extrudable fluoroplastic material, in an embodiment, a perfluoroalkoxyalkane (PFA) copolymer made from comonomers polytetrafluoroethylene and perfluoroalkyl vinyl ether. However, other polymer materials can be used, such as fluoroplastics, such as ethylene trifluorochloroethylene (ECTFE), ethylene tetrafluoroethylene (ETFE), or polyvinylidene fluoride (PVDF).
[0135] In certain embodiments, the support membrane layer 810 comprises individual nanoparticles dispersed at a certain depth within the membrane layer 810, as described above. The nanoparticles allow the support membrane layer to filter at least some pollutants that pass through the filter membrane layer 814, that is, in addition to the filtration provided by the internal filter substrate 812. In other embodiments, the filter substrate 812 and / or the support membrane layer 810 include such nanoparticles. Fluoroplastic materials (e.g., PFA) are very suitable for filters for cleaning semiconductor components, and other environments that require extreme cleanliness and minimize the possibility of contamination. This support membrane is designed to guide the fluid to be filtered to flow along its surface, and to guide the fluid through the structure into the filter substrate below to remove unwanted particles from the filtrate.
[0136] like Fig.9A and 9B As shown, the support film layer 810 may include a plurality of holes 828. The shape of the holes is preferably circular, but it will be appreciated that other shapes are also possible, such as square, rectangular, triangular, etc. The substrate may be wound into a roll, then unwound and directed through a punching machine to form the desired predetermined pattern of holes 828 in the Z direction ( Fig.9A ). Optionally, after being set up, the sheet can be directed through a punch press in a continuous operation to form a predetermined pattern of holes 828 therein.
[0137] refer to Fig. 9B After opening the pores, the filter support member can be stretched in the machine direction, as shown by double-headed arrow 940, to elongate the pores 828 to provide a larger open area for the passage of the fluid to be filtered by the filter media or substrate 812.
[0138] In an optional embodiment, the support membrane layer 810 can be porous (i.e., not having pores 828, or in addition to having pores 828). In this embodiment, additional fluid flow can be achieved through a substantially porous support membrane layer. In an exemplary embodiment, the porosity value of the support membrane layer is at least 0.5 or 50%, preferably at least 0.8 or 80%, and more preferably about 0.86 or 86%. The porosity value is defined as the non-solid or pore volume fraction of the total volume of the material. A more complete description of this composite filter medium can be found in PCT Application Serial No. US2020 / 040941, the complete disclosure of which is incorporated herein by reference in its entirety for all purposes.
[0139] The support membrane layer of the present filter can be prepared by any method known to those skilled in the art. Fig.9A and 9B In one example shown, the support film layer includes ribs. For example, the support film layer can be made by extruding a polymer material to form a sheet and then passing the sheet through a nip area provided by opposing rollers; at least one roller has an outer surface with countersunk grooves. The countersunk grooves in one roller are aligned with the outer surface or the countersunk grooves of the other roller in the nip area to form a ribbed sheet having ribs upstanding from at least one surface of the sheet. Optionally, the ribs can be formed in an extrusion process or a known embossing method. Once the ribs are formed, the support film layer can be wound into a roll, subsequently unwound and directed through a press to form a desired predetermined pattern of holes in the Z direction thereof. Optionally, after setting, the support film layer can be continuously operated to guide the support film layer through a punch press to form a predetermined pattern of holes therein, such as Fig.9A Optionally, the support film layer can be stretched in the machine direction ( Fig. 9B The pores are elongated to provide a larger open area for the passage of a fluid to be filtered through, for example, a filter layer or a substrate.
[0140] Fig.12 The overall system 110 for producing the above-mentioned nonwoven materials and other products is schematically depicted. As shown, the system 110 includes a feeder 120 for advancing a substrate 130 of nonwoven fibers or other materials during the production process. The system 100 also includes a coater 140, a fiberizing system 150, and a heating and / or drying device 160. In certain embodiments, the system 100 also includes a vacuum or other negative pressure source 170 located below the substrate 130, which is opposite to the fiberizing system 150.
[0141] In one embodiment, the feeder 120 includes a winder 122 at the downstream end of the process and an unwinder 124 at the upstream end, which continuously winds the substrate 130 through the system 100. In certain embodiments, the feeder 120 may also include a support surface (not shown) extending between the winders for supporting the substrate 130 as it moves downstream through the system 100. In other embodiments, the substrate is unwound directly from the unwinder 124 to the winder 122 without another support surface.
[0142] The coater 140 is configured to spray droplets of an adhesive or bonding material (e.g., an adhesive or binder) onto the substrate 130 so that the nanoparticles can adhere to the fibers within the substrate 130 to form a stable matrix. The adhesive is preferably present in a relatively small amount to bond individual nanoparticles to the fibers throughout the substrate 130. In a preferred embodiment, the coater 140 includes a nozzle sized to generate adhesive droplets having a diameter of about 20 to 30 microns to increase the penetration depth of the adhesive through the substrate 130. Of course, droplet size may be affected by many other parameters, including air pressure, air volume, air temperature, humidity, spray horn design, rheology / viscosity of the adhesive, carrier, etc.
[0143] Of course, it should be appreciated that coating substrates with adhesives or adhesive materials can be achieved with other coating methods, including ultrasonic spraying, dip coating, spin coating, gravure coating, kiss roll coating, screen coating, powder coating, electrostatic, sputtering coating or similar coating techniques. As described above, the adhesive can comprise a variety of conventional materials, including natural materials (e.g., starch, dextrin, guar gum, etc.) or synthetic resins (e.g., EVA, PVA, PVOH, SBR, etc.). In certain embodiments, a solvent-based adhesive is used, wherein bonding occurs when the solvent evaporates.
[0144] In a preferred embodiment, the adhesive comprises dextrin. In another embodiment, the adhesive comprises a combination of various substances, such as water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzenesulfonate, laurylamine oxide and ammonium hydroxide. In yet another embodiment, the adhesive comprises PVOH. The adhesive can be a solution, an emulsion, a suspension, a hot melt, a curable material, a pure material and / or a combination thereof.
[0145] In some embodiments, adhesive resin is used, and adhesive resin can be cross-linked after adhesive is applied to substrate 130. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when solvent evaporates in adhesive formulation or heat activation in drying process. For some adhesives, crosslinking can be achieved by electromagnetic radiation of high energy wavelength (including but not limited to RF, UV or electron beam). The amount of adhesive can be controlled by adjusting the nozzle size of sprayer 140 or controlling the flow rate of adhesive composition. In some embodiments, adhesive can include surfactant, to reduce the surface or interfacial tension of adhesive, so as to improve its dispersion and wetting properties, and make adhesive more easily penetrate into substrate of certain depth. Suitable surfactant used with adhesive disclosed herein includes nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl) benzene sulfonate, sodium dodecyl benzene sulfonate wetting agent, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphate, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS) etc.
[0146] In some embodiments, sprayer 140 is located upstream of fiberizing system 150 to spray the binder before depositing the nanoparticles. In other embodiments, sprayer 140 is located downstream of fiberizing system 150 to spray the binder after depositing the nanoparticles. In other embodiments, system 100 includes two spray layers; one located upstream of fiberizing system 150, and a second sprayer (not shown) located downstream of fiberizing system 150 to coat substrate 130 with a second binder after depositing the nanoparticles.
[0147] In some embodiments, each sprayer 140 has more than one nozzle head. For example, the nozzle heads can be arranged in series to obtain better uniformity or increase the fiber spray width. Alternatively, the nozzle heads can be placed in parallel (i.e., across the width of the substrate) to ensure that the adhesive is applied to the entire width of the substrate.
[0148] In a preferred embodiment, a negative pressure source or vacuum source (not shown) is arranged below the substrate 130, opposite to the sprayer 140, to increase the penetration depth and uniformity of the adhesive. The negative pressure source can be any suitable suction device that draws the adhesive through the substrate, such as a suction pump, etc.
[0149] In some embodiments, the substrate comprises its own binder composition. In these embodiments, a binder may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers 600, wherein one component comprises a sheath 64 that at least partially surrounds a core 62. In certain embodiments, the sheath 64 and the core 62 may be substantially concentric with each other ( Figure 5AIn other embodiments, the core 84 may not be concentric with the sheath 82 ( Figure 5C In other embodiments, the core 72 and the sheath 74 may be arranged side by side with each other ( Figure 5B ). Of course, other configurations are possible. For example, the core 184 may include a shape other than a circle, such as a dog bone, square, triangle, diamond, etc. Optionally, the fiber 180 may include multiple cores, or may be divided into three, four, or more quadrants.
[0150] Sheath 64 can include materials that bond to nanoparticles. For example, sheath 64 can include materials that become sticky and / or flow when heated and / or dried. During the heating / drying step, the sheath 64 portion of the fiber is heated to its melting point until it becomes sticky and / or flow to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously in drying device 160.
[0151] Fig.13 A fiberizing system 150 for converting a group of nanofibers into individual nanoparticles is schematically shown. As used herein, the term "fiberizing" refers to converting (e.g., opening, separating, isolating, and / or singulating) clusters, clumps, or other groups of nanoparticles that may or may not be entangled with one another into individual nanoparticles having at least one dimension less than 1 micron. Figures 14A-14C shows entangled large nanofiber clusters ( Fig.14A ), tangled clusters of small nanofibers ( Fig. 14B ) and single nanoparticles ( Fig. 14C ) instance.
[0152] As shown, the fiberizing system 150 includes a feeder 200, such as a hopper, for feeding relatively large or large nanoparticle clusters / clumps (see Fig.14A ) is introduced into the system 150. The feeder 200 may include any suitable hopper device known to those skilled in the art, and is preferably configured to introduce large particle clusters into the process at a specific rate, which depends on the fiberization rate downstream. The nanoparticles may be introduced continuously at a specific rate, or at intervals at a specific rate. The large nanoparticle clusters may be broken up before being introduced into the feeder 200.
[0153] It should be appreciated that the nanoparticles can be introduced into the fiberizing device 150 in many different forms. For example, raw nanofibers can be manufactured as long separate fibers. In this form, the nanofibers can be cut to obtain the desired aspect ratio.
[0154] The system 150 also includes a separator 210, such as a blender, for separating or decomposing large nanoparticle clusters / agglomerates into smaller nanoparticle clusters / agglomerates (see Fig. 14B). The feeder 200 delivers the nanofibers to the separator 210 in a stable and continuous state by any mechanical means. The delivery speed will depend on various factors, such as the speed at which the substrate 130 travels along the feeder 120, the fiberization rate of the nanoparticles, etc. By controlling the amount of nanoparticles falling into the separator 210, the amount of nanoparticles dispersed into the substrate can be controlled, thereby achieving a continuous production process.
[0155] In one embodiment, the separator 210 includes a housing 212 having a first opening 214 coupled to the feeder 200 and a second opening 216 coupled to the downstream process. The size of the second opening 216 is preferably to allow only nanofiber clusters of a certain size to pass through. The separator 210 may include a plurality of rotatable blades (not shown) designed to rotate around a vertical axis within the housing 212 to separate and open the coarse nanofiber clusters. The blades may have the same or different pitches and cambers to allow the entangled fibers to be sequentially decomposed or "opened" when going from the first opening 214 to the second opening 216. The fiberizing system 150 also includes an airflow (discussed in more detail below) extending from the separator 210 to the entire system of the nozzle 220. The airflow (together with a series of pumps discussed below) provides the power to move the nanofibers through the system 150. In one embodiment, the airflow is generated by an air compressor 230 configured to supply compressed air to the system, but it should be recognized that other forms of gas can be used to convey the nanofibers through the system 150. The system 150 includes one or more pumps for moving the nanofiber clusters and ultimately individual nanoparticles throughout the system. The pumps may include any suitable pumps, such as positive displacement pumps, centrifugal pumps, axial flow pumps, and the like. In one embodiment, the first pump 240 includes a first inlet fluidly coupled to the air compressor 230 through a first channel 242 and a second inlet fluidly coupled to the separator 210 through a second channel 244. Compressed air is drawn into the first pump 240, which generates a negative pressure (e.g., a vacuum) to draw the nanofiber clusters from the separator 210 into the pump (discussed in more detail below). The system 150 may also include a second pump 250 and a third pump 260, each of which is fluidly coupled to the outlet of the first pump 240. Similarly, the second pump 250 and the third pump 260 generate a negative pressure to pull the nanofiber clusters through the third channel 252.
[0156] In certain embodiments, the pump 240 includes an ejector 300. Fig.15As shown, the ejectors 300 each include a motive fluid inlet 302 and a nanofiber inlet 304, which are coupled to an outlet 306 through a fluid channel 308. The fluid channel 308 includes a converging inlet nozzle 310, a diffuser throat 312, and a diverging outlet diffuser 314. High-pressure, low-speed air is converted into low-pressure, high-speed air, thereby generating the pressure difference required for suction. Based on the Venturi effect and the Bernoulli principle, the primary fluid medium (e.g., compressed air) is used to generate a vacuum to draw the nanofibers into the ejector 300 and discharge them through the outlet 306. The diameter of the ejector 300 depends on the volume flow rate of the compressed air, the suction requirements, the pressure drop, and the fluid pressure of the compressed air.
[0157] review Fig.13 , the third channel 252 includes a joint 254 that divides the third channel 252 into two independent channels, each channel leading to the second pump 250 and the third pump 260. The joint 254 preferably includes a surface or wall arranged substantially perpendicular to the third channel 252 to form a T-shaped intersection. The surface can be any surface that hinders the nanofibers from flowing through the channel, such as the inner wall of the channel at the connection point, or other inner walls with changes in direction, such as curved surfaces, vertical surfaces, etc. Optionally, the channel may include walls or other surfaces arranged in the channel or protruding into the channel in the fluid path. In one embodiment, the channel extends to a roughly T-shaped joint that includes two independent channels extending from the joint. The second ejector is configured to pull the nanofibers into the T-joint at a speed sufficient to break up at least some of the nanofibers.
[0158] As the nanofiber clusters move through the third channel 252, they are pushed toward the surface or wall by the negative pressure applied by the second pump 250 and the third pump 260. The velocity of the nanofibers relative to the joint 254 creates collisions with sufficient kinetic energy to break at least some of the nanofiber clusters into smaller nanofiber clusters and / or individual nanoparticles having at least one dimension less than 1 micron.
[0159] To generate the kinetic energy required to break up the nanofiber clusters, air is propelled through the system 150 at a velocity of about 500 feet per minute (fpm) to about 10,000 feet per minute, preferably about 2,000 fpm to about 6,000 fpm. The system 150 includes a sufficient amount of suction pressure, preferably at least about 20 psi. The suction pressure generates a total pressure of at least about 100 psi throughout the system.
[0160] In certain embodiments, the system 150 further includes a fourth fluid channel 262 and a fifth fluid channel 264 that couple the outlets of the second pump 250 and the third pump 260 to the reactor 270. Fig.16As shown, the reactor 270 includes a top surface 272, a bottom surface 274 and an inner annular chamber 276 extending from the top surface 272 to the bottom surface 274. The reactor 270 also includes a central tube 275, which has an open upper inlet 278 and an outlet 280. The reactor 270 may also include one or more upper outlets 282. The reactor 270 may be coupled to an energy source (not shown) configured to generate a vortex of vortex gas in the annular chamber 276. The energy source may include any appropriate energy source, such as a pump, a compressor, a generator, etc. The vortex gas preferably flows from the bottom to the top of the reactor 270 around the central tube 275 so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 to the top surface 272.
[0161] In another embodiment, the generation of vortex does not require a separate energy source. In this embodiment, nanofiber clusters 290 and individual nanoparticles 292 enter the reactor 270 through bottom inlets 284, 285, 286, 287. The inlets 284, 285, 286, 287 are tilted upward to facilitate the movement of nanofibers and nanoparticles around the central tube 275. In a preferred embodiment, at least one or more of the inlets 284, 285, 286, 287 are tilted so that the nanofibers and nanoparticles are substantially tangent to the central tube 275 when entering the reactor 270. Once the nanofibers and nanoparticles enter the annular chamber 276, their velocity vectors (speed and direction) generate vortices within the reactor 270, causing them to swirl around the central tube 275 and reach the upper portion of the annular chamber 276 upward. The swirling gas preferably flows from the bottom to the top of the reactor 270 around the central tube 275 so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 to the top surface 272. The nanofibers 290 and nanoparticles 292 are blown from the bottom of the reactor to the top without any interference. The vortex in the chamber 276 can further break up (eg, open, separate and / or individualize) the nanofiber clusters 290 as they pass through the reactor 270.
[0162] In some embodiments, the reactor 270 can also be coupled to an energy source (not shown) that is configured to generate a vortex of swirling gas within the annular chamber 276. The energy source can include any suitable energy source, such as a pump, a compressor, a generator, etc. The system 100 can also include another pump or negative pressure source coupled to the upper outlet 282 (see, for example, Fig.17). The negative pressure draws the fibers out of the outlet 282, so that the fibers 290 leave the reactor 270. Since the individual nanoparticles 292 are significantly lighter than the tangled nanofibers 290 that are still gathered together, these individual nanoparticles 292 are sucked into the upper inlet 278 of the central tube 275. At the same time, the larger and heavier nanofiber clusters 290 that have not yet been decomposed are drawn out from the upper outlet 284. The upper outlet 284 can be coupled to another pump (not shown), or to the first pump 240. In this way, the nanofiber clusters 290 are sent back into the process for further decomposition, thereby forming a re-feed system to further decompose the remaining nanofiber clusters.
[0163] The outlet 280 of the central tube 275 is coupled to the nozzle 220 (see Fig.13 ). Individual nanoparticles 292 are sucked into nozzle 220, where they are dispersed onto the substrate surface or into the fiber stream (discussed below). Nozzle 220 may include any suitable nozzle known to those skilled in the art. In one embodiment, nozzle 220 has multiple outlets, the outer dimensions of which are customized according to the size (i.e., area) of the substrate passing through below nozzle 220. Nozzle 220 will disperse the nanoparticles onto the substrate at a rate driven by the pressure of the entire system. In certain embodiments, system 100 includes more than one nozzle coupled to outlet 280 of reactor 270. The nozzles may be arranged on the substrate in any suitable form (e.g., side by side, in series, in parallel, etc.). It should be recognized that pump 240 or pumps 250, 260 may feed the nanofiber / air mixture stream directly into nozzle 220 (i.e., bypassing reactor 270). In this embodiment, the pressure within the system is designed to generate enough kinetic energy to decompose or open substantially all of the nanofibers into individual nanoparticles, thereby eliminating the need for reactor 270 to separate the nanoparticles from larger fiber clusters.
[0164] Reference Fig.17 , another embodiment of the fiberizing system 320 will now be described. As shown, the fiberizing system 320 includes a separator 325 for separating larger or large nanofiber clusters passing through the system 320 into smaller nanofiber clusters. A first ejector 326 is coupled to the outlet of the separator 325 for drawing the nanofibers from the separator 325 into the system 320. An air compressor (not shown) is also coupled to the ejector 326 to provide a motive fluid, as described above. Similar to the previous embodiment, a second ejector 330 and a third ejector 340 are coupled to the outlet of the first ejector 326. The nanofibers are drawn from the first ejector 320 and are pushed toward the surface of the T-junction 350 to break up at least some of the nanofibers into smaller clusters or individual nanoparticles.
[0165] Each of the second and third ejectors 330, 340 has an outlet coupled to another T-junction 360, 370. As before, the nanofibers are pushed toward the surface of the T-junction 360, 370 to further decompose them. The T-junction 360, 370 are each coupled to two fluid channels entering the bottom 380 of the reactor. Therefore, the bottom 380 of the reactor has four separate inlets 382, 384, 386, 388 for the passage of the nanofibers. Each of these inlets is preferably tilted upward and located at an opposite corner of the reactor. This allows the nanofibers to enter the vortex of the reactor and then swirl upward to the upper portion 390 of the reactor.
[0166] As previously referred Fig.16 As described, the reactor includes an annular chamber with a central tube having an open upper end and a lower end coupled to a nozzle. Nanofibers that have been fully decomposed into individual nanoparticles flow through the open upper end and enter the central tube for dispersion through the nozzle. Heavier nanoparticle clusters that have not yet decomposed leave the reactor through one of four independent outlets 392, 394, 396, 398. Ejectors 410, 420 provide the power to extract nanofibers from reactor 400, as described above. Outlets 392, 394 are each coupled to ejector 410 through a T-shaped intersection 412, and outlets 396, 398 are each coupled to ejector 420 through a T-shaped intersection 422. In this case, the nanofibers flow from two channels into one channel when passing through intersections 412, 422.
[0167] The ejectors 410, 420 are each coupled to the T-junctions 430, 440. As previously described, the nanofibers are pushed into the T-junctions 430, 440 to further break them down into individual nanoparticles. Then, the T-junctions 430, 440 are each coupled to the bottom 380 of the reactor 400 (via inlets 432, 434, 442, 444). This allows the nanofibers to return to the reactor 400 for further processing. This process is continued for each nanofiber cluster until it is completely broken down into nanoparticles and enters the nozzle through the central tube. As a final step, the individualized nanofibers are sprayed from the nozzle onto any substrate or mixed with any fiber spinning stream. In this process, the suction is up to 20psi and the pressure is up to 100psi.
[0168] In certain embodiments, fibrosis system 150 may include a separate control system that monitors nanofibers to determine when they are broken down into individual nanoparticles suitable for passing through nozzles. The control system may, for example, simply monitor the pressure of the entire system to ensure that nanofibers are subjected to enough pressure to be broken down into nanoparticles. Alternatively, the control system may include various sensors arranged by the system to detect the characteristics of nanoparticles, such as weight or size. The sensor may be arranged in, for example, reactor 400 so that the control system may control the various parameters of reactor 400, such as the negative pressure applied to outlet 392,394,396,398, the speed of the eddy current of the annular chamber, or the pressure applied to the center tube that nanoparticles are sucked into the nozzle. Fig.18 Another embodiment of the system 500 for producing multilayer nonwoven material is shown. As shown, system 500 comprises first and second unwinders 502, 504 and single winder 506, and winder 506 is used for winding first and second substrates 510, 512 downstream of system 500. As in previous embodiments, system 500 can also include a support surface (not shown) for each substrate 510, 512. First and second unwinders 502, 504 are used to advance first and second substrates 510, 512 into the process, wherein they are connected together and then wound on single winder 506, as described below. System 500 comprises first sprayer 520 and second sprayer 522, which are located downstream of first unwinder 502 and second unwinder 504 respectively, for applying adhesive to first substrate 510 and second substrate 512. The system 500 also includes a first fiberizing system / device 530 and a second fiberizing system / device 532, which are located downstream of each spray gun 520, 522. As previously discussed, the fiberizing devices 530, 532 generate individual nanoparticles and disperse these nanoparticles onto the substrates 510, 512. After the nanoparticles are dispersed into the substrates 510, 512, the two substrates are connected together at a connection point 540 so that they are propelled downstream together. The two substrates can be bonded to each other at this point, or they can simply be placed one on top of the other.
[0169] The system 500 also includes a heater / drying device, such as an IR oven 550, located downstream of the connection point 540 of the two substrates. The heating / drying device heats and dries the two substrates to bond them to each other and to bond the nanoparticles to the fibers within the substrates. The substrates can, for example, be laminated to each other.
[0170] In certain embodiments, nanoparticles are dispersed in two substrates 510, 512. In such an embodiment, system 500 is designed so that nanoparticles are dispersed by the first surface of each substrate. Then, substrates can be connected together so that the first surface faces each other. Alternatively, the first surface can be opposite to each other (that is, substrate is connected at the second relative surface of each substrate). In another embodiment again, the first surface of the first substrate is connected to the second surface of the second substrate.
[0171] Fig.19 A filtration product 700 is shown, comprising a filter medium 710 of a nonwoven material, comprising fibers 722 and nanoparticles 720 dispersed in at least a portion of the filter medium 710. As shown, the filter medium 710 has a first upper surface 712 and a second lower surface 714. The nanoparticles have been dispersed through the upper surface 712 so that they extend beyond the upper surface 712 and into the filter medium 710 to a certain depth, as described above. The filtration product 700 also includes a support layer 730, which can be any suitable support layer known in the art, such as a substantially rigid polymer that provides support for the filter medium 710, or an open membrane having a plurality of pores for gas or fluid to pass through (as described above).
[0172] Fig. 20 Another filtration product 740 is shown that includes a filter media 710 of a nonwoven material including fibers 722 and nanoparticles 720 dispersed in a portion of the filter media 710. In this embodiment, the product 740 includes a scrim layer 750 bonded to a support layer 730.
[0173] Fig.21 A dual layer filtration product 760 is shown, which includes first and second filter media 762, 764 bonded to each other. As shown, nanoparticles 720 have been dispersed in a certain depth of each filter medium 762, 764. In this embodiment, the nanoparticles 720 have been dispersed through the inner surface 766, 768 of the filter media 762, 764. In another embodiment (not shown), the nanoparticles are dispersed through the outer surface 770, 772 of the filter media 762, 764. In yet another embodiment, the nanoparticles 720 can be deposited on the inner surface 766 of the medium 762 and the outer surface 772 of the medium 764.
[0174] In yet another aspect, the system for making nonwoven material comprises a first device for producing one or more fiber streams and a second device for isolating nanoparticles in a gaseous medium. The second device is dispersed into the nanoparticles in the stream, and the stream is fed to the fiber stream to form the nonwoven material. The system can also include a dispersing device, for example a nozzle, which is coupled to the second device, and is configured to feed the nanoparticles substantially uniformly into the fiber stream. The fiber stream can be produced with any suitable mechanism known in the art, for example meltblowing, spunbonding or spunlace, thermal bonding, combing, air-laid, wet-laid, extruded, co-molded, acupuncture, stitching, hydraulic entanglement, etc.
[0175] In one example, the system can include a spunbond line, wherein filaments are formed by spinning and stretching molten polymer. The fiber bundles of the filaments are separated and spread out, and then layered on a net to form a web. The fibers are bonded in the form of a sheet by thermal bonding and embossing. The first stream 630 can be introduced, for example, before the attenuation zone or before the bonding (consolidation) process.
[0176] In another embodiment, the system can include two carding machines arranged in series with each other. The first stream 630 can be introduced at any point after the first carding line and before the second carding line, so that the nanoparticles are sandwiched between the two carded fiber webs. Afterwards, all fibers (including the nanoparticles) are bonded together in a hot air bonding oven (the nanoparticles are thermally interlocked).
[0177] Fig. 22 Another embodiment for generating one or more fiber streams is shown. In this embodiment, nanoparticles are dispersed between two meltblowing dies where molten polymer is pushed through small holes to make fibers. When the nanoparticles encounter the fibers while they are still sticky, they mechanically entangle with the fibers and thermally bond to the fibers. Therefore, in some embodiments, no additional bonding process is required.
[0178] like Fig. 22 As shown, the apparatus 600 for forming a fibrous nonwoven structure comprises a fiberizing system 610 similar to one of the above-described systems and devices. The fiberizing system 610 comprises a nozzle 620 or similar device for dispersing individual nanoparticles into a first stream 630. The apparatus 600 also comprises a system for generating one or more fiber streams that will be combined with the single nanoparticle stream 630. The system may comprise any system known in the art, such as spunbonding, carding, extrusion, etc.
[0179] In another embodiment, the device includes a first feeder and a second feeder, such as a hopper 640, 642, coupled to a first extruder 650 and a second extruder 652. For example, each extruder may include an extrusion screw (not shown) driven by a conventional drive motor (not shown). When the polymer advances through the extruders 650, 652, the extrusion screw is rotated by the drive motor, so the polymer is gradually heated to a molten state. Thermoplastic polymers are heated to a molten state and can be completed in multiple non-discrete steps, and when they advance to two melt-blown dies 660, 662 respectively by the discrete heating zones of the extruders 650, 652, their temperature gradually increases. Melt-blown dies 660, 662 can be another heating zone, in which the temperature of the thermoplastic resin is maintained at a higher level for extrusion.
[0180] Each meltblowing die 660, 662 is configured so that the two attenuating air streams of each die converge to form a single air stream that entrains and attenuates the molten strands as they flow from the small holes or orifices 672 in the meltblowing die. The molten strands 20 are attenuated into fibers or, depending on the degree of attenuation, into microfibers, which have a relatively small diameter, typically smaller than the diameter of the orifices 672. Thus, each meltblowing die 660, 662 has a corresponding single primary air stream 680, 690 containing entrained and attenuated polymer fibers.
[0181] The main gas streams 680, 690 containing polymer fibers are aligned to converge at the forming zone 700. In addition, a first stream 630 of individual nanoparticles is added to the two main gas streams 680, 690 of thermoplastic polymer fibers or microfibers at the forming zone 30. The introduction of the individual nanoparticles into the two main gas streams 680, 690 of fibers is intended to produce a distribution of secondary fibrous materials 32 in the combined main gas streams 680, 690 of fibers. This can be achieved by merging the first stream 630 of individual nanofibers between the two main gas streams 680, 690 so that all three gas streams converge in a controlled manner.
[0182] Examples of suitable meltblowing dies that can be used to make nonwoven materials are discussed in more detail in U.S. Patent Nos. 6,972,104, 8017534, and 7772456, and U.S. Patent Application No. US20200216979A1, the entire disclosures of which are incorporated herein by reference in their entirety.
[0183] Embodiment 1 is a filter medium comprising a substrate comprising fibers; nanoparticles are arranged within the substrate, wherein the nanoparticles have at least one dimension less than 1 micron; and wherein at least one of the fibers or the nanoparticles is electrostatically charged.
[0184] Embodiment 2 is the filter medium of embodiment 1, wherein the fibers are electrostatically charged.
[0185] Embodiment 3 is the filter medium of any one of embodiments 1 to 2, wherein the nanoparticles are electrostatically charged. In any embodiment disclosed herein, the substrate, the nanoparticles, or both are electrostatically charged.
[0186] Embodiment 4 is the filter medium of any one of embodiments 1 to 3, wherein the substrate comprises a triboelectric filter medium. Embodiment 5 is the filter medium of any one of embodiments 1 to 4, wherein the fibers are corona charged. Embodiment 6 is the filter medium of any one of embodiments 1 to 5, wherein the substrate is a triboelectric filter medium, and wherein the triboelectric filter medium is formed by carding and needle punching. Embodiment 7 is the filter medium of embodiment 6, wherein the nanoparticles and the fibers are needle punched together.
[0187] Embodiment 8 is the filter medium of any one of embodiments 1 to 7, wherein the substrate comprises a spunbond charged media. Embodiment 9 is the filter medium of any one of embodiments 1 to 8, wherein the substrate comprises a meltblown charged media.
[0188] Embodiment 10 is the filter medium of any one of embodiments 1 to 9, wherein the substrate comprises a mesh material. In any embodiment disclosed herein, the substrate may include a mesh, a fabric, a knitted fabric, a nonwoven, or a sheet.
[0189] Embodiment 11 is the filter media of any of embodiments 1 to 10, wherein the fibers have a linear density of about 3 denier or greater. Embodiment 12 is the filter media of any of embodiments 1 to 11, wherein the fibers have a linear density of at least about 5 denier. In any embodiments disclosed herein, the fibers of the substrate can include fibers of two or more different sizes.
[0190] Embodiment 13 is the filter media of any of embodiments 1 to 12, wherein the fibers are biocomponent fibers having a core and a sheath.
[0191] Embodiment 14 is the filter media of any of embodiments 1 to 13, wherein the fiber is a bicomponent fiber having a core and a sheath, and wherein the core is not concentric with the sheath.
[0192] Embodiment 15 is the filter medium of any one of embodiments 1 to 14, wherein at least some of the nanoparticles are arranged from a first surface to a second surface opposite the first surface within the substrate. Embodiment 16 is the filter medium of any one of embodiments 1 to 15, wherein the nanoparticles form a gradient within the substrate such that the density of individual nanoparticles decreases from the first surface to the second surface opposite the first surface. Embodiment 17 is the filter medium of any one of embodiments 1 to 15, wherein the nanoparticles are substantially uniformly dispersed throughout the fibrous substrate.
[0193] Embodiment 18 is the filter medium of any one of embodiments 1 to 17, wherein the nanoparticles are isolated in the fluid and dispersed through the first surface of the substrate.
[0194] Embodiment 19 is the filter medium of any one of embodiments 1 to 18, wherein the nanoparticles are selected from the group consisting of carbon fibers, glass fibers, polypropylene fibers, nylon fibers, polylactide fibers, and combinations thereof.
[0195] Embodiment 20 is the filter medium of any one of embodiments 1 to 19, further comprising a binder within the fiber material that binds the nanoparticles to the fibers. Embodiment 21 is the filter medium of any one of embodiments 1 to 19, further comprising a binder, and wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and a synthetic resin. Embodiment 22 is the filter medium of any one of embodiments 1 to 19, wherein the fibers comprise a binder composition that binds the nanoparticles to the fibers.
[0196] Embodiment 23 is an air filtration product comprising the filter medium of any one of embodiments 1 to 22.
[0197] Embodiment 24 is a filter medium comprising a substrate comprising fibers and nanoparticles, wherein the substrate mechanically filters contaminants; and wherein the substrate electrostatically filters contaminants.
[0198] Embodiment 25 is the filter medium of embodiment 24, wherein the nanoparticles mechanically filter contaminants. Embodiment 26 is the filter medium of any one of embodiments 24-25, wherein the fibers are electrostatically charged.
[0199] Embodiment 27 is the filter medium of any one of embodiments 24 to 26, wherein the substrate comprises a triboelectric filter medium.
[0200] Embodiment 28 is the filter medium of any one of embodiments 24 to 27, wherein the substrate is a triboelectric filter medium, and wherein the triboelectric filter medium is formed by carding and needle punching. Embodiment 29 is the filter medium of any one of embodiments 24 to 28, wherein the nanoparticles and the fibers are needle punched together.
[0201] Embodiment 30 is the filter medium of any one of embodiments 24 to 29, wherein the substrate comprises a spunbond charged media. Embodiment 31 is the filter medium of any one of embodiments 24 to 30, wherein the substrate comprises a meltblown charged media.
[0202] Embodiment 32 is the filter medium of any one of embodiments 24 to 31, wherein the substrate comprises a mesh material. In any embodiment disclosed herein, the substrate can be a mesh, a fabric, a knitted fabric, a nonwoven, or a sheet.
[0203] Embodiment 33 is an air filtration product comprising the filter medium of any one of embodiments 24 to 32.
[0204] Embodiment 34 is a method for making a filter medium, the method comprising providing a substrate comprising fibers; electrostatically charging the fibers; and dispersing nanoparticles in the substrate.
[0205] Embodiment 35 is the method of embodiment 34, further comprising corona charging the fibers. Embodiment 36 is the method of embodiment 34, further comprising tribocharging the fibers. Embodiment 37 is the method of embodiment 34, further comprising electrostatically spinning the fibers. Embodiment 38 is the method of embodiment 34, further comprising needling the fibers and the nanoparticles together. Embodiment 39 is the method of embodiment 34, further comprising combing the fibers.
[0206] Embodiment 40 is the method of any one of embodiments 34 to 39, further comprising spunbonding the fibers. Embodiment 41 is the method of any one of embodiments 34 to 40, further comprising meltblowing the fibers.
[0207] Embodiment 42 is the method of any one of embodiments 34 to 41, further comprising dispersing the nanoparticles onto the first surface of the substrate such that the nanoparticles penetrate at least the first surface of the substrate.
[0208] Embodiment 43 is the method of any one of embodiments 34 to 42, further comprising isolating individual nanoparticles in the fluid, wherein the individual nanoparticles have at least one dimension less than 1 micron.
[0209] Example 1
[0210] A microfiber substrate of bicomponent fibers is provided in the form of a roll, having an inner circular portion of polyester and an outer concentric portion of HDPE. In a roll-to-roll process, the substrate is sprayed with an adhesive and nanofibers or nanoparticles of biosoluble glass fibers are deposited. The nonwoven product is then placed in an oven for heating, and the cooled nonwoven product is collected onto another roll.
[0211] According to the following Figure 12-16 The nanoparticles were deposited by the process described in . In the experiments, biosoluble glass nanofibers were used. The nanofibers had a diameter of about 700 nanometers and a length of about 500 micrometers. In the following examples, a carded hot air bonded nonwoven made of bicomponent fibers was used as the substrate:
[0212] Flat sheet filter media samples were tested at a filtration velocity of 110 fpm. Sample size was 12" x 12". NaCl salt particles ranging from 0.3 to 10 microns were used as the contaminant.
[0213] Example 2
[0214] A carded nonwoven made of 3-denier PET / PE bicomponent fibers was used as a substrate. A composition comprising water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide was used as a binder. Different nanofiber addition amounts were controlled by adjusting the line speed.
[0215] Table 1
[0216]
[0217] This example shows that by controlling the amount of nanoparticles added, the MERV rating can be increased from MERV 7 to MERV 13.
[0218] Example 3
[0219] A high loft hot air bonded carded nonwoven with 5 denier bicomponent fibers was used as the substrate. A typical starch adhesive was diluted and sprayed before nanofiber deposition. As the solvent evaporated and dried under an IR heater, the starch fully bonded the nanofibers.
[0220] Table 2
[0221]
[0222] Example 4
[0223] Use spunbond or meltblown media as a substrate, wherein nanoparticles are incorporated into the substrate after IPA discharge, as described herein. Spunbond fibers are made of a molten polymer that is spun and stretched to produce filaments. The average basis weight of the substrate is about 90gsm, and the average thickness is about 0.57mm. Use a base sample without any nanoparticles incorporated. Prepare 4 separate samples, which include nanoparticles incorporated into the substrate, as described herein. In sample 2, nanoparticles are incorporated into meltblown fibers after IPA discharge. In samples 1, 3, and 4, nanoparticles are incorporated into spunbond fibers after IPA discharge. The test results are shown in Table 3 below.
[0224] Table 3
[0225]
[0226] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles is higher than that of the base samples, and the efficiency of the E2 and E3 particle groups is significantly improved. Using nanoparticles, the overall MERV rating of the samples is improved from MERV 7 (base sample) to MERV 12 to MERV 16. The pressure drop of the base sample without nanoparticles is 0.07 inches of water column. The pressure drop of samples 1-4 increased slightly, ranging from 0.17 to 0.41 inches of water column. In sample 2, where nanoparticles are incorporated into meltblown fibers, the MERV rating is 14 and the pressure drop is 0.24 inches of water column.
[0227] Example 5
[0228] A 5 denier hot through bonded carded fiber was used as the substrate. A base sample without nanoparticles incorporated was used. Two separate samples were prepared that included nanoparticles incorporated into the substrate as described herein. The test results are shown in Table 4 below.
[0229] Table 4
[0230] Sample No. Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.31 57% 90% 98% 13 2 5D carded fiber 0.33 61% 92% 98% 13
[0231] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was significantly improved over the base samples. The use of nanoparticles increased the overall MERV rating of the samples from MERV 6 (base sample) to MERV 13. The pressure drop of the base sample without nanoparticles was 0.03 inches of water column. The pressure drop of samples 1 and 2 increased slightly, ranging from 0.31 to 0.33 inches of water column.
[0232] Example 6
[0233] Meltblown fibers were used as substrates. The average basis weight of the substrate was about 24 gsm and the average thickness was about 0.4 mm. A base sample without nanoparticles or adhesives (e.g., PVOH) was used. Sample 1 included meltblown fibers with the tape side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 2 included meltblown fibers with the velvet side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 3 included meltblown fibers with PVOH sprayed thereon, and nanoparticles were incorporated into the fibers, as described herein. The test results are shown in Table 5 below.
[0234] Table 5
[0235]
[0236]
[0237] As shown, in all three particle groups, especially in the E1 particle group, the efficiency of sample 3 incorporating nanoparticles increased compared to the other three base samples. The overall MERV rating of sample 3 increased from MERV 13 or 14 (base samples) to MERV 15 (using nanoparticles). The PVOH added to samples 2 and 3 did not significantly increase the pressure drop (i.e., 0.35 for the base sample, 0.38 and 0.41 for samples 1 and 2). The pressure drop of sample 3 did increase from about 0.40 inches of water column to about 1 inch of water column. In sample 3 incorporating nanoparticles into the meltblown fiber, the MERV rating was 15 and the pressure drop was 1.02 inches of water column.
[0238] Example 7
[0239] 5 denier hot through bonded carded fibers were used as the substrate. A base sample without nanoparticles was used. Seven additional samples were prepared, which included 5 denier carded fibers with nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 6 below.
[0240] Table 6
[0241] Sample No. Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.07 7% 31% 69% 7 2 5D carded fiber 0.09 5% 36% 69% 7 3 5D carded fiber 0.15 16% 51% 77% 9 4 5D carded fiber 0.16 21% 58% 81% 10 5 5D carded fiber 0.17 31% 70% 90% 11 6 5D carded fiber 0.28 46% 85% 96% 12 7 5D carded fiber 0.32 58% 91% 97% 13
[0242] As shown, the seven samples incorporating nanoparticles had higher efficiencies than the base samples in all three particle groups, especially in the E2 and E3 particle groups. The overall MERV rating increased from MERV 6 (base samples) to MERV 7 to MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.32 inches of water column.
[0243] Example 8
[0244] High loft spunbond fibers were used as substrates in continuous fiber production lines. This test included two different versions: 205-6 and 205-2, in which the settings on the continuous fiber production line were changed to produce two substrates with different weights and thicknesses. Each version (205-6 and 205-2) used a base sample without nanoparticles incorporated. Six additional samples were prepared, which included 205-6 and 205-2 fibers and nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 7 below.
[0245] Table 7
[0246] Sample No. Substrate PD E1 E2 E3 MERV Base 205-6 0.04 0% 9% 43% 6 Base 205-2 0.04 0% 8% 37% 6 1 205-6 0.86 88% 98% 99% 15 2 205-2 0.48 79% 96% 99% 14 3 205-6 0.87 82% 97% 99% 14 4 205-2 0.42 61% 90% 98% 13 5 205-6 0.78 79% 97% 99% 14 6 205-2 0.23 44% 79% 96% 11
[0247] As shown, in all three particle groups, the six samples incorporating nanoparticles showed significant improvements in efficiency over the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 11 to MERV 14 (with nanoparticles). The pressure drop only increased from 0.04 inches of water column to a maximum of 0.87 inches of water column. The pressure drop in the 205-2 sample only increased to a maximum of 0.48 inches of water column.
[0248] Example 9
[0249] Spunbond and meltblown fibers were used as substrates. For spunbond fibers, the average basis weight of the substrate was about 70 gsm, while for meltblown fibers, the average basis weight of the substrate was about 24 gsm. The average thickness of the substrate was about 0.75 mm. A base sample without nanoparticles was used. Five additional samples were prepared, including spunbond and meltblown fibers and nanoparticles incorporated into the fibers, as described herein. In samples 1-3, nanoparticles were sprayed onto meltblown fibers. In samples 4 and 5, nanoparticles were sprayed onto spunbond fibers. In addition, in samples 1 and 2, the adhesive PVOH was not sprayed onto the substrate. PVOH was sprayed onto samples 3-5. The test results are shown in Table 8 below.
[0250] Table 8
[0251] Sample No. Substrate PD E1 E2 E3 MERV Base Spunbond+MB 0.07 2% 17% 29% 5 1 Spunbond+MB 0.41 100% 100% 100% 16 2 Spunbond+MB 0.56 100% 100% 100% 16 3 Spunbond+MB 0.26 99% 100% 100% 16 4 Spunbond+MB 0.4 100% 100% 100% 16 5 Spunbond+MB 0.17 97% 100% 100% 16
[0252] As shown, in all three particle groups, the five samples incorporating nanoparticles showed a significant improvement in efficiency over the base samples. The overall MERV rating increased from MERV 5 (base sample) to MERV 16 (with nanoparticles). The pressure drop only increased from 0.07 inches of water column to a maximum of 0.56 inches of water column. In samples 3-5 (PVOH sprayed onto the substrate), the pressure drop only increased to a maximum of 0.4 inches of water column.
[0253] Example 10
[0254] 5 denier hot air bonded carded glass fiber was used as the substrate. A base sample without nanoparticles was used. Three additional samples were prepared, which included 5 denier carded glass fibers and nanoparticles incorporated therein. The test results are shown in Table 9 below.
[0255] Table 9
[0256] Sample No. Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.27 59% 91% 99% 13 2 5D carded fiber 0.18 45% 83% 98% 12 3 5D carded fiber 0.24 54% 89% 99% 13
[0257] As shown, in all three particle groups, the three samples incorporating nanoparticles showed a significant improvement in efficiency over the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 12 or MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.27 inches of water column.
[0258] Embodiment 11
[0259] A fiber mixture of 5 denier and 7 denier hot air bonded combed glass fibers was used as the substrate. The medium was hot air bonded. A base sample without nanoparticles was used. Nineteen additional samples were prepared, which included a fiber mixture of 5 denier and 7 denier combed glass fibers and nanoparticles incorporated therein. The test results are shown in Table 10 below.
[0260] Table 10
[0261]
[0262]
[0263] As shown, in all three particle groups, all 19 samples incorporating nanoparticles showed significant improvements in efficiency over the base samples. The overall MERV rating increased from MERV 6 (baseline samples) to MERV 10 to MERV 13 (using nanoparticles) (most samples were rated MERV 13). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.31 inches of water column.
[0264] Although the apparatus, system and method are described in detail in accordance with certain preferred embodiments thereof herein, those skilled in the art will be able to make numerous modifications and variations therein. Therefore, the foregoing description should not be interpreted as being limited thereto, but rather should be interpreted as including the obvious variations described above, and only limited by the spirit and scope of the following claims.
Claims
1. A filter medium comprising: a substrate comprising fibers; nanoparticles disposed within the substrate, wherein the nanoparticles have at least one dimension less than 1 micron; and At least one of the fibers or the nanoparticles is electrostatically charged.
2. The filter medium of claim 1, wherein the fibers are electrostatically charged. The filter medium of claim 1 , wherein the nanoparticles are electrostatically charged.
4. The filter media of claim 1, wherein the substrate comprises a triboelectric filter media.
5. The filter media of claim 1, wherein the fibers are corona charged.
6. The filter medium of claim 4, wherein the triboelectric filter medium is formed by carding and needle punching.
7. The filter medium of claim 6, wherein the nanoparticles and the fibers are needled together.
8. The filter media of claim 1, wherein the substrate comprises a spunbond tape dielectric.
9. The filter media of claim 1, wherein the substrate comprises a meltblown charged media.
10. The filter media of claim 1, wherein the substrate comprises a mesh material.
11. The filter media of claim 1 , wherein the fibers have a linear density of approximately 3 denier or greater.
12. The filter media of claim 1, wherein the fibers have a linear density of at least about 5 denier.
13. The filter media of claim 1, wherein the fibers are biocomponent fibers having a core and a sheath.
14. The filter media of claim 13, wherein the core is not concentric with the sheath.
15. The filter media of claim 1, wherein at least some of the nanoparticles are disposed within the substrate from a first surface to a second surface opposite the first surface.
16. The filter media of claim 15, wherein the nanoparticles form a gradient within the substrate such that the density of individual nanoparticles decreases from a first surface to a second surface opposite the first surface.
17. The filter media of claim 15, wherein the nanoparticles are substantially uniformly dispersed throughout the fibrous substrate.
18. The filter media of claim 1, wherein nanoparticles are isolated in a fluid and dispersed through the first surface of the substrate.
19. The filter media of claim 1, wherein the nanoparticles are selected from the group consisting of carbon fibers, glass fibers, polypropylene fibers, nylon fibers, polylactide fibers, and combinations thereof.
20. The filter media of claim 1, further comprising a binder within the fiber material, the binder binding nanoparticles to the fibers.
21. The filter medium of claim 20, wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.
22. The filter media of claim 1, wherein the fibers comprise a binder composition that binds the nanoparticles to the fibers.
23. An air filter article comprising the filter medium of claim 1.
24. A filter medium comprising: a substrate comprising fibers and nanoparticles, wherein the substrate mechanically filters contaminants; and The substrate filters pollutants electrostatically.
25. The filter media of claim 24, wherein the nanoparticles mechanically filter contaminants.
26. The filter media of claim 24, wherein the fibers are electrostatically charged.
27. The filter media of claim 24, wherein the substrate comprises a triboelectric filter media.
28. The filter media of claim 27, wherein the tribocharged filter media is formed by carding and needle punching.
29. The filter media of claim 28, wherein the nanoparticles and the fibers are needled together.
30. The filter media of claim 24, wherein the substrate comprises a spunbond tape dielectric.
31. The filter media of claim 24, wherein the substrate comprises a meltblown charged media.
32. The filter media of claim 24, wherein the substrate comprises a mesh material.
33. An air filter product comprising the filter medium of claim 24.
34. A method of making a filter medium, the method comprising: providing a substrate comprising fibers; electrostatically charging the fibers; as well as Nanoparticles are dispersed in the substrate.
35. The method of claim 34, further comprising corona charging the fibers.
36. The method of claim 34, further comprising tribocharging the fibers.
37. The method of claim 34, further comprising electrospinning the fibers.
38. The method of claim 34, further comprising needling the fibers and the nanoparticles together.
39. The method of claim 34, further comprising combing the fibers.
40. The method of claim 34, further comprising spunbonding the fibers.
41. The method of claim 34, further comprising melt blowing the fibers.
42. The method of claim 34, further comprising dispersing the nanoparticles onto a first surface of the substrate such that the nanoparticles penetrate at least the first surface of the substrate.
43. The method of claim 42, further comprising isolating a single nanoparticle in a fluid, wherein the single nanoparticle has at least one dimension less than 1 micron.
Citation Information
Patent Citations
Multilayer filter medium for filter, method for producing the same, and air filter
US10252201B2
Durable nanofiber synthetic filter media
US10799820B2
Integrated nanofiber filter media
US20090266759A1
Wind turbine
US20200040941A1
Multi-die melt blowing system for forming co-mingled structures and method thereof
US20200216979A1
Cited By
Filterelement
DE102024002169A1